GeoDaRT: Contextual geospatial data infrastructure for distributed on-farm experimentation - Phillip Lanza; David G. Rossiter; Diana S. Sinton; Louis Longchamps (Computers and Electronics in Agriculture, 2026)

Semi‐Natural Habitats Buffer the Effects of Crop Diversification on Arthropod Pest Control Services in Agricultural Landscapes - Thomas Perrot; Léa Beaumelle; Eva Thomine; Yann Tricault; Nicolas Desneux; Matthias Albrecht; Péter Batáry; Felix Bianchi; Klaus Birkhofer; Aliette Bosem Baillod; Rebecca Chaplin‐Kramer; Anne‐Marie Cortesero; et al. (Ecology Letters, 2026)
Crop diversification is a promising strategy to strengthen pest control services in agricultural landscapes. Diversifying crops may limit pests through host crop dilution or by enhancing top‐down control by their enemies. However, crop diversification may also benefit generalist pests through higher resource continuity. Using a large‐scale dataset encompassing 742 landscapes across 13 countries, we assessed the impact of landscape‐scale crop diversity on the abundance of natural enemies, the potential for biological control, and insect pest abundance. Crop diversification did not increase the overall abundance of natural enemies or the potential for biological pest control. Instead, crop diversity primarily favoured the abundance of specialist natural enemies and pests in highly simplified landscapes, an effect that was reduced in landscapes with high proportions of semi‐natural habitats. Lastly, low proportions of host crops in the landscape were associated with higher abundances of natural enemies. Taken together, our results indicate that crop diversification is not a ‘one size fits all’ strategy to control agricultural pests, and that other landscape characteristics, such as high amounts of semi‐natural habitats, must be considered to enhance biological pest control services.

Comprehensive Phenotypic and Genomic Study for Understanding the Variability in Susceptibility of Listeria monocytogenes to AMPs and Bacteriocins - Omar Fliss; Louis-David Guay; Nguyen Phuong Pham; Philippe Leprohon; Natalie Fava; Franco Pagotto; Marc Ouellette; Éric Biron; Ismail Fliss (Probiotics and Antimicrobial Proteins, 2026)

Introduced or established? Convergent evidence indicates imported pine wood nematode vectors occupy gaps in native distribution - Jean-Claude Grégoire; Jean Artois; Julien Claude; Marius Gilbert; Serge Morand; Géraldine Roux; Gilles San Martin; Dimitrios Avtzis; Nick Berkvens; Jochem Bonte; Hans Casteels; Sandra Closa; et al. (Journal of Pest Science, 2026)
Monitoring regulated quarantine plant pathogens and, when relevant, their vectors is compulsory in the European Union. Local Monochamus species (Coleoptera, Cerambycidae) vector the pine wood nematode, Bursaphelenchus xylophilus , a non-native pest already established in most of Portugal. Only 29 M. galloprovincialis individuals were trapped in Belgium in ten years (2013–2022), despite a dense coverage of pheromone-baited traps, suggesting absence or a very rare local occurrence in the country. In the northern neighbouring countries, only one single established population is known in The Netherlands and one in Denmark. A species distribution model based on pheromone-trap catches (negative and positive) of M. galloprovincialis from 4,914 traps in 29 European countries between 2008 and 2019 was developed, using the overall climate conditions and the distribution of seven pine tree species as explanatory variables. The effect of spatial scale was tested with a multi-scale approach. With a 225*225 km spatial grain, the major explanatory variables were the mean diurnal temperature range and, to a lesser extent, the presence of Pinus spp. The model predicted a low probability of presence in Belgium, the Netherlands, Great Britain and north-western Germany compared to southern Europe. Genotyping allowed to conclude that at least some of the beetles caught in Belgium originated from foreign locations. All catches were located close to entry points, suggesting introduction with imported material. The small size of most of the Belgian pine stands may also explain the absence or apparently transient status, or rareness of Monochamus spp. This study thus suggests that surveys in Belgium should privilege entry points rather than local forest stands.

Impact of acute sleep restriction on resting ventilation and cytokine levels in normobaric hypoxia, and their association - Louis David; Julianne Touron; Marie-Claire Erkel; Catherine Drogou; Anaïs Pontiggia; Vincent Beauchamps; Carine Malle; Olivier Nespoulous; Ulysse Comte; Alexandra Malgoyre; Fabien Sauvet; Beth A. Beidleman; et al. (European Journal of Applied Physiology, 2026)

Processing and End-Uses of Wood Affected by Forest Fires, Eastern Spruce Budworm and Mountain Pine Beetle Outbreaks - Rosilei Garcia; Isabelle Duchesne; Louis-David Giasson; Alain Cloutier (Current Forestry Reports, 2026)
Purpose of review This review provides an overview of current forest fires and insect outbreaks in North America, examining how these disturbances affect wood quality over time. It highlights two of the most destructive insect pests: the eastern spruce budworm (SBW) and the mountain pine beetle (MPB). The article also examines the challenges of processing disturbance-affected wood and explores its potential uses in lumber, engineered wood products, and wood-based panels. Recent findings Forest fires have intensified and become more frequent in recent years, especially in temperate and boreal forests. Unprecedented SBW outbreaks have also been reported in Eastern Canada. While MPB outbreaks have decreased since 2019, they remain cyclical, indicating the possibility of future resurgences. From 2023 to 2025, these disturbances affected over 60 million hectares in Canada, resulting in significant tree damage and mortality. Although disturbance-affected wood can still be used for lumber and high-value products, its quality deteriorates over time while it remains in the forest, particularly after a fire. Manufacturing products from such wood is difficult due to its low moisture content, changed properties, and high defect rate. Summary Disturbance-affected wood typically has lower moisture content, increased permeability, greater brittleness, and a higher incidence of defects, such as insect holes, blue stain, decay, and checks, compared to wood from sound trees. These characteristics can negatively impact lumber recovery and grading and reduce its suitability for secondary manufacturing of wood products like laminated veneer lumber, plywood, or oriented strand board. Nonetheless, this type of wood can be transformed into value-added products such as particleboard, fiberboard, or cross-laminated timber, especially when used in limited proportions or in hybrid compositions. Further research is needed to understand how the properties of disturbance-affected wood change over time and how these changes affect the production of various products. Furthermore, optimizing log sorting, conversion processes, and manufacturing techniques to account for the unique characteristics of disturbance-affected wood is important to ensure the quality and performance of the final products.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Bidirectional associations between biological aging, cardiovascular health, and cardiovascular risk: findings from the INSPIRE-T lifespan cohort - Mathilde Strumia; Vanina Bongard; Samuel Thuriot; Philippe Cestac; Brigitte Sallerin; Jean-Marc Lemaitre; David Furman; Sophie Guyonnet; Bruno Vellas; Sandrine Andrieu; Laure Rouch; Sophie Guyonnet; et al. (GeroScience, 2026)
Chronological age is a common and non-modifiable factor for chronic disease, but does not fully explain age-related changes. Biological clocks have been developed to explore biological aging mechanisms. They could help identify protective factors against accelerated aging and associated diseases. We aim to assess the association between reduced epigenetic or inflammatory aging and ideal cardiovascular health or cardiovascular risk. We conducted a cross-sectional analysis of participants from the INSPIRE-T cohort. Cardiovascular health (CVH) was assessed using the Life’s Essential 8 score. Cardiovascular risk was assessed using the American Framingham risk score (FRS) and the European Systematic Coronary Risk Evaluation (SCORE2) score. Epigenetic and inflammatory aging was calculated from the residuals from linear regression of biological age (based on five epigenetic clocks and one inflammatory clock) and chronological age. Linear and logistic regression models were used. Better CVH has been associated with slower epigenetic aging, particularly in younger subjects and men. Accelerated epigenetic aging measured by GrimAge was associated with an increase cardiovascular risk (for SCORE2: OR = 1.10 95%CI [1.04; 1.16]). No persistent association was found with the inflammatory clock. Our study reported an association between ideal global CVH with reduced epigenetic aging after adjustment for chronological age and gender. This suggests that epigenetic aging may be modifiable through healthy lifestyle and cardiovascular risk management, although a potential underlying causal relationship remains to be established. Moreover, accelerated epigenetic aging is linked to worsening cardiovascular risk, and could be a new risk factor alongside chronological age. Graphical Abstract

Suspended particulate matter in Voh lagoon (New Caledonia): Impact of ultramafic rock mining on primary production - Sandrine Chifflet; Jean-Louis Gonzalez; David Varillon; Anne Desnues; Bernard Angeletti; Adrien Duvivier; Doriane Delanghe; Cristèle Chevalier (Regional Studies in Marine Science, 2026)

A parametric life-cycle model for assessing environmental impacts of 4G and 5G cellular base stations - Louis Golard; Robin Dethienne; Jérôme Louveaux; David Bol (The International Journal of Life Cycle Assessment, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A phylogenomic and metagenomic meta-analysis of bacterial diversity in the phyllosphere lifts a veil on hyphomicrobiales dark matter - Jean-Baptiste Leducq; Louis-Philippe St-Amand; David Ross; Steven W. Kembel (Systematic and Applied Microbiology, 2026)

Small methane emissions from pasture observed with eddy covariance and flux-gradient methods: are they real or artefacts? - Johannes Laubach; Aaron M. Wall; John E. Hunt; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; Louis A. Schipper (Agricultural and Forest Meteorology, 2026)

Correlation of coalescence times in a diploid Wright–Fisher model with recombination and selfing - David Kogan; Dimitrios Diamantidis; John Wakeley; Louis Wai-Tong Fan (Theoretical Population Biology, 2026)

The Siwaliks: Reading Rodent Evolution in the Miocene of South Asia - Catherine Badgley; John Barry; Anna K. Behrensmeyer; Lawrence J. Flynn; Louis L. Jacobs; Yuri Kimura; Michèle E. Morgan; David Pilbeam; S. Mahmood Raza; Nikos Solounias (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The NASA VIIRS burned area product, global validation, and intercomparison with the NASA MODIS burned area product - Louis Giglio; Luigi Boschetti; David P. Roy; Joanne V. Hall; Maria Zubkova; Michael Humber; Haiyan Huang; Vladyslav Oles (Remote Sensing of Environment, 2025)

Lowering foliage nitrogen contents reduces N2O emissions in grazed pastures: An emission factor-based modelling assessment constrained by eddy covariance measurements - Lìyǐn L. Liáng; Aaron M. Wall; Donna L. Giltrap; Miko U.F. Kirschbaum; Jordan P. Goodrich; David I. Campbell; Louis A. Schipper (Agricultural Systems, 2025)

Periodic cropping of pasture for summer-grazed turnips leads to substantial carbon loss - Aaron M. Wall; Jordan P. Goodrich; Seager Ray; David I. Campbell; Louis A. Schipper (Agricultural and Forest Meteorology, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Climate information to action: Challenges for Baltic beach management - David Cabana; Louis Celliers (Ocean & Coastal Management, 2025)

Enhancing prioritization strategies of natural extracts: integrating heterogeneous data from metabolomics datasets and biological screenings into knowledge graphs - Luis-Manuel Quiros-Guerrero; Frederic Burdet; Olivier Kirchhoffer; Paola Haemmerli; Louis-Felix Nothias; Pierre-Marie Allard; Arnaud Gaudry; Jahn Nitschke; Nabil Hanna; Sébastien Moretti; Robin Engler; Florence Mehl; et al. (Phytochemistry Letters, 2025)

The phytochemical diversity of wild hops from northern France for potential brewing application - Augustin Bildstein; Mathilde Vandenberghe; Anne-Sophie Paguet; Gabriel Lefèvre; Louis Raymond; Gaëtan Kientz; Jennifer Samaillie; Franck Michels; Séverine Derbré; Cécile Palaric; David Mathiron; Marie-Laure Fauconnier; et al. (Phytochemistry Letters, 2025)

Pharmacognosy in the digital era: exciting opportunities offered by metabolomics and accessible digitised data - Jean-Luc Wolfender; Arnaud Gaudry; Adriano Rutz; Luis Quiros-Guerrero; Olivier A. Kirchhoffer; Laurence Marcourt; Bruno David; Antonio Grondin; Emerson Ferreira Queiroz; Louis-Félix Nothias; Pierre-Marie Allard (Phytochemistry Letters, 2025)

Spatial distributions of acoustic scattering groups during the warm-to-cold transition period in the Senegal coastal ecosystem and their relationships with environmental variables - Viviane David; Jérémie Habasque; Gildas Roudaut; Louis Marie; Delphine Thibault; Anne Lebourges-Dhaussy; Xavier Capet; Eric Machu (Journal of Marine Systems, 2025)

Correction to: Incremental efficacy systematic review and meta-analysis of psilocybin-for-depression RCTs - Nicholas C. Borgogna; Tyler Owen; Dan Petrovitch; Jacob Vaughn; David A. L. Johnson; Louis A. Pagano; Stephen L. Aita; Benjamin D. Hill (Psychopharmacology, 2025)

Incremental efficacy systematic review and meta-analysis of psilocybin-for-depression RCTs - Nicholas C. Borgogna; Tyler Owen; Dan Petrovitch; Jacob Vaughn; David A. L. Johnson; Louis A. Pagano; Stephen L. Aita; Benjamin D. Hill (Psychopharmacology, 2025)
Rationale Psilocybin is a potentially paradigm-shifting depression intervention. We conducted a systematic review and meta-analysis of psilocybin-for-depression randomized controlled trials (RCTs). Objectives Systematically assess harm reporting, risk of bias, action mechanism specification, and incremental therapeutic effect sizes in the psilocybin-for-depression RCT literature. Methods Assessed databases included PsycINFO, CINAHL, Embase, Medline, Web of Science, and Scopus. Search terms “Psilocybin” or “Psychedelic” were paired with “Depression”, and "Randomized Controlled Trial" or “RCT”. Results We identified k = 9 RCTs ( k = 10 subgroups) involving n = 602 participants (56% psilocybin). Five studies had low/very low harm quality reporting, opposed to two with high. Most studies demonstrated a high risk of bias. Therapeutic mechanisms of action (MoAs) were discussed in varying detail but rarely assessed in original publications. Psilocybin was moderately superior to controls at reducing depression ( g = 0.62; 95% CI = 0.27, 0.98). Effects were heterogenous (τ = .47). Smaller studies evidenced stronger effects that favored psilocybin (Egger’s b 0 = 3.63, p = .014). Almost all studies documented financial conflicts of interests. Conclusion Psilocybin demonstrates significant depression reduction relative to controls. However, researchers, clinicians, and stakeholders should consider several contextual factors. Effects were moderate and attenuated in larger and better-controlled studies. Harms reporting and risk of bias was high, though partly driven by unique challenges of psilocybin research. MoAs were variably specified but rarely assessed; suggesting it is unclear how depression is reduced. We advise researchers conduct RCTs with active control conditions, larger samples, and include MoA assessments. Independent RCTs from researchers without financial conflicts of interest are needed.

Improving Medical Education in Oncology: Enhancing Students’ Understanding of Cancer Treatments Through Multidisciplinary Clinical Rotations - Arnaud Beddok; Leila Bouazzi; Coralie Barbe; Pierre Martin; Julian Gratiaux; Philippe Guilbert; Louis Job; Amélie Lemoine; David Morland; Dimitri Papathanassiou; Stéphane Perin; Yacine Merrouche; et al. (Journal of Cancer Education, 2025)

Impact of Human Activities and Forest Biomass on Atmospheric Carbon Dioxide: A Mathematical Model - David Mbelle Ngoh; Anjali Jha; Bring; A. K. Misra; Dany-Pascal Moualeu Ngangue; Louis Aimé Fono (Environmental Modeling & Assessment, 2025)

Mixture analysis of associations between environmental and workplace toxins and liver damage and telomere length, stratified by race/ethnicity - Ning Ma; Rowena Yip; Mark Woodward; Sara Lewis; Michael Crane; Artit Jirapatnakul; Costica Aloman; Meena B. Bansal; Douglas Dieterich; Louis Gros; Damaskini Valvi; Elena Colicino; et al. (Journal of Environmental Sciences, 2025)

Mechanically coupled distributed dynamic strain measurement for track systems and earthworks - David Milne; Ali Masoudi; John Harkness; Ben Lee; Geoff Watson; Louis Le Pen; Gilberto Brambilla; William Powrie (Transportation Geotechnics, 2025)

Switzerland's individual municipalities' suitability for the soon-to-be introduced cleaner energy production regulation allowing peer-to-peer solar electricity trading markets: implications for sustainable development - Kim Follonier; Louis-David Benyayer; Yacine Rekik (Journal of Cleaner Production, 2025)

Variation of phenotypic disparity over the ontogeny of coral reef fish populations - Léa Vignaud; Bruno Frédérich; Mehdi Boudault; Amelia Chatagnon; Pierre-Louis Rault; Sébastien Cordonnier; David Lecchini; Charlotte R. Dromard (Marine Biology, 2025)

Effects of point‐source discharges on shortfin eels ( Anguilla australis ) along the Waikato River, New Zealand - David W. West; Brendan J. Hicks; Nicholas Ling; Michael R. van den Heuvel; Louis A. Tremblay (New Zealand Journal of Marine and Freshwater Research, 2025)
The Waikato River is the longest river in New Zealand and is exposed to range of anthropogenic stressors. This study investigated the effects of three major point‐source discharges on resident shortfin eels Anguilla australis along the river. Shortfin eels were caught from sites upstream and downstream of discharges of bleached kraft mill effluent (BKME) from pulp and paper manufacture, sewage, and a thermal power plant. At each site, population parameters (relative abundance and age structure) and individual metrics of health such as condition factor and organ (gonad, liver, and spleen) to somatic weight ratios were measured. Blood, biochemical (hepatic 7‐ethoxyresorufin‐ O ‐deethylase or EROD) and chemical markers (bile chemistry and trace elements in flesh) were also measured. Measures of exposure and response to discharges confirmed that the shortfin eels were resident at the sites sampled. The discharges had few negative impacts on individual eel health and positive responses were seen to warm water discharge. However, resident shortfin eels were immature so reproductive responses could not be determined. In conclusion, shortfin eels in this study showed few responses to the effects of the discharges except for increased resin acids, bile polycyclic aromatic hydrocarbons, and EROD at the BKME site.

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

HADAD: Hexagonal A-Star with Differential Algorithm Designed for weather routing - Javier Jiménez de la Jara; Daniel Precioso; Louis Bu; M. Victoria Redondo-Neble; Robert Milson; Rafael Ballester-Ripoll; David Gómez-Ullate (Ocean Engineering, 2025)

Metabolomic monitoring of chicory during in vitro gastrointestinal digestion and correlation with bioactive properties - Céline L. Pouille; Camille Dugardin; Josette Behra; Melissa Tourret; Roland Molinié; Jean-Xavier Fontaine; David Mathiron; Cécile Palaric; David Gagneul; Rozenn Ravallec; Caroline Rambaud; Jean-Louis Hilbert; et al. (Food Chemistry, 2025)

A Study Of the effect of Sex on drug dosing, concentrations, and pharmacogenomics in the Montreal Heart Institute Hospital Cohort (SOS-PGx): methodology and research progress - Marc-Olivier Pilon; Jessica Hindi; Isabelle St-Jean; Martin Jutras; Maxime Meloche Brouillette; Ian Mongrain; Caroline Lagacé; Karla Vazquez; Sylvie Provost; Louis-Philippe Lemieux Perreault; Essaid Oussaid; David Busseuil; et al. (European Journal of Clinical Pharmacology, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Cirrhotic Patients Exhibit Remarkable Vascular Regenerative Profile One Month after Liver Transplantation - Daniel Eyraud; Aurélien Philippe; Coralie Guerin; Ignacio Sarmiento; Ludovic Suner; Louis Puybasset; Sébastien Bertil; Jean-Christophe Vaillant; Dominique Helley; Benjamin Granger; David M. Smadja; Pascale Gaussem (Stem Cell Reviews and Reports, 2025)

Sources of low-frequency δ18O variability in coastal ice cores from Dronning Maud Land (Antarctica) - Stéphane Vannitsem; David Docquier; Sarah Wauthy; Matthew Corkill; Jean-Louis Tison (Climate Dynamics, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Polymer Beads Increase Field Responses to Host Attractants in the Dengue Vector Aedes aegypti - Elizabeth F. Adhiambo; Louis-Clement Gouagna; Eunice A. Owino; Francis Mutuku; Merid N. Getahun; Baldwyn Torto; David P. Tchouassi (Journal of Chemical Ecology, 2024)

Soil solution chemistry weak response to long-term N addition points towards a strong resilience of northeastern American forests to past and future N deposition - Daniel Houle; Marie Renaudin; Louis Duchesne; Jean-David Moore; Apolline Benoist (Science of The Total Environment, 2024)

A new airborne system for simultaneous high-resolution ocean vector current and wind mapping: first demonstration of the SeaSTAR mission concept in the macrotidal Iroise Sea - David L. McCann; Adrien C. H. Martin; Karlus A. C. de Macedo; Ruben Carrasco Alvarez; Jochen Horstmann; Louis Marié; José Márquez-Martínez; Marcos Portabella; Adriano Meta; Christine Gommenginger; Petronilo Martin-Iglesias; Tania Casal (Ocean Science, 2024)
Coastal seas, shelf seas and marginal ice zones are dominated by small-scale ocean surface dynamic processes that play a vital role in the transport and exchange of climate-relevant properties such as carbon, heat, water and nutrients between land, ocean, ice and atmosphere. Mounting evidence indicates that ocean scales below 10 km have far-ranging impacts on air–sea interactions, lateral ocean dispersion, vertical stratification, ocean carbon cycling and marine productivity – governing exchanges across key interfaces of the Earth system, the global ocean, and atmosphere circulation and climate. Yet, these processes remain poorly observed at the fine spatial and temporal scales necessary to resolve them. The Ocean Surface Current Airborne Radar (OSCAR) is a new airborne instrument with the capacity to inform these questions by mapping vectorial fields of total ocean surface currents and winds at high resolution over a wide swath. Developed for the European Space Agency (ESA), OSCAR is the airborne demonstrator of the satellite mission concept SeaSTAR, which aims to map total surface current and ocean wind vectors with unprecedented accuracy, spatial resolution and temporal revisit across all coastal seas, shelf seas and marginal ice zones. Like SeaSTAR, OSCAR is an active microwave synthetic aperture radar along-track interferometer (SAR-ATI) with optimal three-azimuth sensing enabled by unique highly squinted beams. In May 2022, OSCAR was flown over the Iroise Sea, France, in its first scientific campaign as part of the ESA-funded SEASTARex project. The campaign successfully demonstrated the capabilities of OSCAR to produce high-resolution 2D images of total surface current vectors and near-surface ocean vector winds, simultaneously, in a highly dynamic, macrotidal coastal environment. OSCAR current and wind vectors show excellent agreement with ground-based X-band-radar-derived surface currents, numerical model outputs and NovaSAR-1 satellite SAR imagery, with root mean square differences from the X-band radar better than 0.2 m s−1 for currents at 200 m resolution. These results are the first demonstration of simultaneous retrieval of total current and wind vectors from a high-squint three-look SAR-ATI instrument and the first geophysical validation of the OSCAR and SeaSTAR observing principle. OSCAR presents a remarkable new ocean observing capability to support the study of small-scale ocean dynamics and air–sea interactions across the Earth's coastal, shelf and polar seas.

Exploring the determinants of disaster and climate resilience building in Zimbabwe’s rural communities - Louis Nyahunda; Livhuwani David Nemakonde; Sizwile Khoza (Natural Hazards, 2024)
With the burgeoning threats from natural hazards and extreme weather events driven by climate change in every section and sector of society, building resilience against disasters and risks posed by climate change has become an unescapable discourse. The study’s main thrust is to establish the determinants of resilience building in Zimbabwe’s rural communities. The study adopted the qualitative constructivist grounded theory approach in conjunction with participatory action research to gain insights from community members and traditional leaders. A total of forty-six participants from Chimanimani District, Zimbabwe participated in the study. The findings revealed that the availability of natural and human resources, collective efficacy, government and development agency support systems, indigenous knowledge systems, and livelihood diversification were crucial determinants of resilience building for rural communities in Zimbabwe. The identified determinants for resilience building signal that these determinants need to be harnessed to inform policy and practice interventions. Furthermore, the availability of the identified determinants implies that rural communities can minimise, and prevent losses, reduce exposure to natural hazards, disasters and climate change risks and manage the impacts of natural hazards whenever they emerge. The study recommends that these determinants be complemented by access to technology, resilient community infrastructures, robust social protection systems, and hazard risk assessment participatory processes by rural communities. In addition, effective emergency and health services, among other contingent measures essential to improve community resilience.

Climbing the green ladder in Sub-Saharan Africa: dynamics of financial development, green energy, and load capacity factor - Louis David Junior Annor; Margarita Robaina; Elisabete Vieira (Environment Systems and Decisions, 2024)

Wheat dwarfing reshapes plant and fungal development in arbuscular mycorrhizal symbiosis - Pierre-Louis Alaux; Pierre-Emmanuel Courty; Hélène Fréville; Jacques David; Aline Rocher; Elisa Taschen (Mycorrhiza, 2024)

Effects of dairy farming management practices on carbon balances in New Zealand’s grazed grasslands: Synthesis from 68 site-years - Aaron M. Wall; Johannes Laubach; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; John E. Hunt; Paul L. Mudge; David Whitehead; Louis A. Schipper (Agriculture, Ecosystems & Environment, 2024)

Simulation of soil temperature under maize: An inter-comparison among 33 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2024)

Methane emissions from animal agriculture: Micrometeorological solutions for challenging measurement situations - Johannes Laubach; Thomas K. Flesch; Christof Ammann; Mei Bai; Zhiling Gao; Lutz Merbold; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; John E. Hunt; Aaron M. Wall; Louis A. Schipper (Agricultural and Forest Meteorology, 2024)

The challenge of assessing the effects of drifting fish aggregating devices on the behaviour and biology of tropical tuna - Amaël Dupaix; Frédéric Ménard; John D. Filmalter; Yannick Baidai; Nathalie Bodin; Manuela Capello; Emmanuel Chassot; Hervé Demarcq; Jean‐Louis Deneubourg; Alain Fonteneau; Fabien Forget; Francesca Forrestal; et al. (Fish and Fisheries, 2024)
Fishers have intensively used drifting fish aggregating devices (DFADs) over the last three decades to facilitate their catch of tropical tunas. DFADs increase purse‐seine efficiency, potentially increasing tuna fishing mortality. They could also have impacts on tuna natural mortality and reproductive potential, and assessing the consequences of their presence at sea on tuna populations is a challenge. The use of DFADs results in a major increase in the number of floating objects, which are spatially heterogeneous at sea. To date, no converging scientific results exist regarding the effects of DFADs on the large‐scale movements and behaviour of tuna, mainly due to the difficulty of disentangling the respective roles of DFADs and environmental factors. Some biological indices show that tuna condition is lower when associated to a floating object than in a free‐swimming school. However, it is not clear whether this is the cause or the consequence of the association nor if it has long‐term effects on individuals' fitness. Further scientific progress requires (i) the collection of time series of indicators to monitor habitat change, individual behaviour, individual fitness, and population dynamics and (ii) experimental studies to identify the underlying behavioural and biological processes involved in associative behaviour. The extent of the modification of the surface habitat by the massive deployment of DFADs and the current uncertainty of the possible long‐term consequences on the individual fitness and dynamics of tuna populations argue for the need for increased awareness of this issue by Regional Fisheries Management Organisations regulating tuna fishing.

Indoor comfort management and energy consumption in Arctic buildings: Occupant perceptions in an indigenous community of Canada - Alice Cavalerie; David Dumas; Louis Gosselin (Building and Environment, 2024)

Bioplastic degradation and assimilation processes by a novel bacterium isolated from the marine plastisphere - Valérie Barbe; Justine Jacquin; Madeleine Bouzon; Adèle Wolinski; Gabrielle Derippe; Jingguang Cheng; Corinne Cruaud; David Roche; Stéphanie Fouteau; Jean-Louis Petit; Pascal Conan; Mireille Pujo-Pay; et al. (Journal of Hazardous Materials, 2024)

Assessing collaboration, knowledge exchange, and stakeholder agency in coastal governance to enhance climate resilience - Lena Rölfer; Louis Celliers; Meredith Fernandes; Nina Rivers; Bernadette Snow; David J. Abson (Regional Environmental Change, 2024)
Coastal governance plays a central role in building the capacities for adaptation and transformation towards climate resilience in coastal social-ecological systems (SES). However, enhancing climate resilience requires effective coordination between organisations involved in coastal governance. Therefore, more information about the role and agency of organisations and the relationships between them is needed. This paper aims to improve the understanding of collaboration, knowledge exchange, and stakeholder agency for enhancing climate resilience in coastal SES, using a case study in Algoa Bay, South Africa. We apply and combine stakeholder analysis and social network analysis, which is currently underrepresented in climate change adaptation research. Results suggest that different top-down and bottom-up processes are needed to improve knowledge exchange and enhance climate resilience in the coastal governance of the Algoa Bay SES. These include improved leadership, effective knowledge transfer, integration of climate information, support for bridging organisations, and inclusivity of marginalised stakeholders. These suggestions may also be more broadly applicable and transferable to similar coastal SES. Ultimately, the results of this study shed light on network structures in coastal governance facing climate change and advance research on combining stakeholder analysis and social network analysis in climate change adaptation and environmental governance research.

Atmospheric effects are stronger than soil moisture in restricting net CO2 uptake of managed grasslands in New Zealand - Jordan P. Goodrich; Aaron M. Wall; David I. Campbell; Margaret M. Barbour; Johannes Laubach; John E. Hunt; Louis A. Schipper (Agricultural and Forest Meteorology, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Financial development, inclusive growth, and environmental quality: emerging markets perspective - Louis David Junior Annor; Margarita Robaina; Elisabete Vieira (Environment, Development and Sustainability, 2023)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Assessment of cyclic superposition approaches for the cyclic design of monopiles supporting offshore wind turbines - Louis-Marin Lapastoure; Andrea Diambra; Soroosh Jalilvand; David Igoe (Ocean Engineering, 2023)

Comparative planetology – Comparing cirques on Mars and Earth using a CNN - Joshua M. Williams; Louis A. Scuderi; Timothy P. McClanahan; Maria E. Banks; David M.H. Baker (Geomorphology, 2023)

Characterizing Substrate-Borne Vibrational Mating Signals Produced by Pear Psylla, Cacopsylla pyricola (Hemiptera: Psyllidae) - Dowen Mae I. Jocson; Mark T. Gonzales; David R. Horton; Louis B. Nottingham; Elizabeth H. Beers; Liesl C. Oeller; David W. Crowder (Journal of Insect Behavior, 2023)
Tactics that manipulate insect behavior are a component of many pest management strategies. Pheromone-based mating disruption is one such tactic widely used in agricultural systems, but few studies have assessed disrupting other mate communication mechanisms, such as acoustic signals. The most destructive pear pest in the Pacific Northwest USA, pear psylla ( Cacopsylla pyricola ) is believed to use acoustic signals to find mates, making it a candidate for this type of disruption. This species has two adult morphs, overwintering adults (winterforms) that emerge in the spring and subsequent generations (summerforms). Our study characterized the mating signals for both sexes and morphs of pear psylla, and assessed whether temperature and previous exposure to adult conspecifics altered signals and likelihood of signaling. While there are descriptions for acoustic signals of other psyllid species, this study provides the first evidence that C. pyricola communicates acoustically. The two sexes communicate via duetting; males signal to attract a female and the female signals back if she is receptive for mating. We showed that both morphotypes’ male signals contain a group of chirps followed by a trill, while females respond with chirps . Male signal trills differed significantly in frequency (Hz) between winterform and summerform psylla. The signal frequency among morphs also had a positive linear relationship with temperature, suggesting that dissimilarity in signals among morphs had some relationship to temperature. Males were more likely to signal when they had previous exposure to females compared to males without exposure to females. Our results provide new information on how pear psylla communicate acoustically for mating, advancing the potential to develop mating disruption strategies for integrated pest management (IPM).

Decreased Synaptic Vesicle Glycoprotein 2A Binding in the Human Postmortem Essential Tremor Cerebellum: Evidence of Reduction in Synaptic Density - Yanghong Yang; Chao Zheng; Baosheng Chen; Nora C. Hernandez; Phyllis L. Faust; Zhengxin Cai; Elan D. Louis; David Matuskey (The Cerebellum, 2023)

Physical and numerical investigation of integral bridge abutment stiffness due to seasonal thermal loading - Sha Luo; Ziyan Huang; Yazan Asia; Flavia De Luca; Raffaele De Risi; John Harkness; Louis Le Pen; Geoff Watson; David Milne; David Chapman; Anastasios Sextos; Nicole Metje; et al. (Transportation Geotechnics, 2023)

Dreissena polymorpha responses under thermal and hypoxic stress: New insights in the tolerance of this freshwater sentinel species - Fanny Louis; Damien Rioult; Béatrice Rocher; Véronique Gaillet; Laurence Delahaut; Séverine Paris-Palacios; Elise David (Aquatic Toxicology, 2023)

Importance of relative binding of bisphenol A and bisphenol S to plasma proteins for predicting their in vivo potencies - Véronique Gayrard; Catherine Viguie; Nicolas Cabaton; Elodie Person; Daniel Zalko; Flore Grandin; Alain Berrebi; David Metsu; Pierre-Louis Toutain; Nicole Picard-Hagen (Toxicology and Applied Pharmacology, 2023)

Point-light display: a new tool to improve verb recovery in patients with aphasia? A pilot study - Victor Francisco; Frédéric Louis; Romain David; Maxime Billot; Anne-Laure Rouquette; Lucie Broc; Christel Bidet-Ildei (Experimental Brain Research, 2023)

The impact of occupational exposure to crystalline silica dust on respiratory function (airway obstruction and FEF25-75) in the French general population - Pierre-Marie Wardyn; Jean-Louis Edme; Virginie de Broucker; Nathalie Cherot-Kornobis; David Ringeval; Philippe Amouyel; Annie Sobaszek; Luc Dauchet; Sébastien Hulo (Environmental Research, 2023)

Simulation of evapotranspiration and yield of maize: An inter-comparison among 41 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2023)

Controls on methylmercury concentrations in lakes and streams of peatland‐rich catchments along a 1700 km permafrost gradient - Lauren M. Thompson; McKenzie A. Kuhn; Johanna C. Winder; Lucas P. P. Braga; Ryan H. S. Hutchins; Andrew J. Tanentzap; Vincent L. St. Louis; David Olefeldt (Limnology and Oceanography, 2023)
Permafrost thaw may increase the production of neurotoxic methylmercury (MeHg) in northern peatlands, but the downstream delivery of MeHg is uncertain. We quantified total mercury (THg) and MeHg concentrations in lakes and streams along a 1700 km permafrost transect in boreal western Canada to determine the influence of regional permafrost extent compared to local lake and catchment characteristics. In lakes, we assessed sediment microbial communities and modeled potential rates of water column photodemethylation (PD). Regardless of permafrost conditions, peatlands were the primary sources of MeHg across the transect as MeHg concentrations in streams increased with aromatic dissolved organic carbon (DOC), iron, and lower pH. Higher DOC and greater catchment peatland extent were further associated with higher stream %MeHg (MeHg/THg). Peatland lakes were potential MeHg sinks, with lower MeHg concentrations than streams (mean ± 1SD: 0.19 ± 0.23 and 0.47 ± 0.77 ng MeHg L −1 , respectively), and larger stream catchments had lower %MeHg where PD may occur in abundant small lakes. Microbial communities in lake sediments showed that abundance of Hg reducing genes ( mer A) predominated over Hg methylating ( hgc A) and MeHg demethylating ( mer B) genes. The effects of permafrost extent on MeHg processes in lakes were secondary to the influence of local catchment characteristics, but lakes in regions with less permafrost had higher DOC concentrations, higher %MeHg, and lower potential rates of PD. Our study highlights a need to understand the impacts of climate change on MeHg source and sink processes, particularly as mediated through changes to peatland DOC, to improve projections of future MeHg concentrations in northern catchments.

Atmospheric Correction Inter-comparison eXercise, ACIX-II Land: An assessment of atmospheric correction processors for Landsat 8 and Sentinel-2 over land - Georgia Doxani; Eric F. Vermote; Jean-Claude Roger; Sergii Skakun; Ferran Gascon; Alan Collison; Liesbeth De Keukelaere; Camille Desjardins; David Frantz; Olivier Hagolle; Minsu Kim; Jérôme Louis; et al. (Remote Sensing of Environment, 2023)

Development and Evaluation of High-Density SNP Arrays for the Eastern Oyster Crassostrea virginica - Ximing Guo; Jonathan B. Puritz; Zhenwei Wang; Dina Proestou; Standish Allen; Jessica Small; Klara Verbyla; Honggang Zhao; Jaime Haggard; Noah Chriss; Dan Zeng; Kathryn Lundgren; et al. (Marine Biotechnology, 2023)

CO2 and H2S absorption in aqueous MDEA with ethylene glycol: Electrolyte NRTL, rate-based process model and pilot plant experimental validation - Karen Gonzalez; Louis Boyer; David Almoucachar; Bénédicte Poulain; Eric Cloarec; Christophe Magnon; Frédérick de Meyer (Chemical Engineering Journal, 2023)

Thirteen novel ideas and underutilised resources to support progress towards a range‐wide American eel stock assessment - David K. Cairns; José Benchetrit; Louis Bernatchez; Virginie Bornarel; John M. Casselman; Martin Castonguay; Anthony R. Charsley; Malte Dorow; Hilaire Drouineau; Jens Frankowski; Alex Haro; Simon D. Hoyle; et al. (Fisheries Management and Ecology, 2022)
A robust assessment of the American eel ( Anguilla rostrata ) stock, required to guide conservation efforts, is challenged by the species’ vast range, high variability in demographic parameters and data inadequacies. Novel ideas and underutilised resources that may assist both analytic assessments and spatially oriented modelling include (1) species and environmental databases; (2) mining of data from scattered sources; (3) infilling of data gaps by spatial analysis; (4) age estimation from measurements of DNA methylation; evaluation of eel abundance by (5) larval, (6) glass‐bottom boat, (7) net enclosure and (8) eDNA surveys; (9) accounting for dam‐induced habitat increases in eel watercourse modelling; (10) spatially oriented modelling with and without temporal components; (11) geographically nested modelling of glass eel recruitment; (12) spawner per recruit modelling and (13) life cycle modelling to examine larval allocation effects. Eel biologists are too few to gather the required assessment data across all of the species’ range. Public posting of electrofishing and eDNA metabarcoding data sets and the use of machine learning techniques to comprehensively inventory small dams will help meet some data needs. These approaches address only a small proportion of the assessment challenges that face American eels. Worldwide collaboration amongst Anguilla scientists is a key enabler of progress towards stock assessment goals.

Correction to: Forest Genetics Research in the Mediterranean Basin: Bibliometric Analysis, Knowledge Gaps, and Perspectives - Bruno Fady; Edoardo Esposito; Khaled Abulaila; Jelena M. Aleksic; Ricardo Alia; Paraskevi Alizoti; Ecaterina-Nicoleta Apostol; Phil Aravanopoulos; Dalibor Ballian; Magda Bou Dagher Kharrat; Isabel Carrasquinho; Marwan Cheikh Albassatneh; et al. (Current Forestry Reports, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Forest Genetics Research in the Mediterranean Basin: Bibliometric Analysis, Knowledge Gaps, and Perspectives - Bruno Fady; Edoardo Esposito; Khaled Abulaila; Jelena M. Aleksic; Ricardo Alia; Paraskevi Alizoti; Ecaterina-Nicoleta Apostol; Phil Aravanopoulos; Dalibor Ballian; Magda Bou Dagher Kharrat; Isabel Carrasquinho; Marwan Cheikh Albassatneh; et al. (Current Forestry Reports, 2022)
Purpose of Review Recognizing that in the context of global change, tree genetic diversity represents a crucial resource for future forest adaptation, we review and highlight the major forest genetics research achievements of the past decades in biodiversity-rich countries of the Mediterranean region. For this, we conducted a bibliometric analysis of the scientific literature spanning the past thirty years (1991–2020). Putting together the representative regionwide expertise of our co-authorship, we propose research perspectives for the next decade. Recent Findings Forest genetics research in Mediterranean countries is organized into three different scientific domains of unequal importance. The domain “Population diversity and Differentiation” related to over 62% of all publications of the period, the domain “Environmental conditions, growth and stress response” to almost 23%, and the domain “Phylogeography” to almost 15%. Citation rate was trending the opposite way, indicating a strong and sustained interest in phylogeography and a rising interest for genetics research related to climate change and drought resistance. The share of publications from Asia and Africa to the total within the Mediterranean increased significantly during the 30-year period analyzed, reaching just below 30% during the last decade. Summary Describing poorly known species and populations, including marginal populations, using the full potential of genomic methods, testing adaptation in common gardens, and modeling adaptive capacity to build reliable scenarios for forest management remain strategic research priorities. Delineating areas of high and low genetic diversity, for conservation and restoration, respectively, is needed. Joining forces between forest management and forest research, sharing data, experience, and knowledge within and among countries will have to progress significantly, e.g., to assess the potential of Mediterranean genetic resources as assisted migration material worldwide. Introductory quote: Let us collect with care the facts we can observe, let us consult experience wherever we can, and when this experience is inaccessible to us, let us assemble all the inductions which observation of facts analogous to those which escape us can furnish and let us assert nothing categorically; in this way, we shall be able little by little to discover the causes of a multitude of natural phenomena, and, perhaps, even of phenomena which seem the most incomprehensible... J.B. de Lamarck (Philosophie zoologique, 1809), cited by O. L anglet (1971).

Epimutation in inherited metabolic disorders: the influence of aberrant transcription in adjacent genes - Jean-Louis Guéant; Youssef Siblini; Céline Chéry; Guillaume Schmitt; Rosa-Maria Guéant-Rodriguez; David Coelho; David Watkins; David S. Rosenblatt; Abderrahim Oussalah (Human Genetics, 2022)

Ocular manifestations in patients with inborn errors of intracellular cobalamin metabolism: a systematic review - Karim Matmat; Rosa-Maria Guéant-Rodriguez; Abderrahim Oussalah; Arnaud Wiedemann-Fodé; Carlo Dionisi-Vici; David Coelho; Jean-Louis Guéant; Jean-Baptiste Conart (Human Genetics, 2022)

Chemical analysis of trace elements at the nanoscale in samples recovered from laser-heated diamond anvil cell experiments - Ingrid Blanchard; Sylvain Petitgirard; Vera Laurenz; Nobuyoshi Miyajima; Max Wilke; David C. Rubie; Sergey S. Lobanov; Louis Hennet; Wolfgang Morgenroth; Rémi Tucoulou; Valentina Bonino; Xuchao Zhao; et al. (Physics and Chemistry of Minerals, 2022)
High pressure and high temperature experiments performed with laser-heated diamond anvil cells (LH-DAC) are being extensively used in geosciences to study matter at conditions prevailing in planetary interiors. Due to the size of the apparatus itself, the samples that are produced are extremely small, on the order of few tens of micrometers. There are several ways to analyze the samples and extract physical, chemical or structural information, using either in situ or ex situ methods. In this paper, we compare two nanoprobe techniques, namely nano-XRF and NanoSIMS, that can be used to analyze recovered samples synthetized in a LH-DAC. With these techniques, it is possible to extract the spatial distribution of chemical elements in the samples. We show the results for several standards and discuss the importance of proper calibration for the acquisition of quantifiable results. We used these two nanoprobe techniques to retrieve elemental ratios of dilute species (few tens of ppm) in quenched experimental molten samples relevant for the formation of the iron-rich core of the Earth. We finally discuss the applications of such probes to constrain the partitioning of trace elements between metal and silicate phases, with a focus on moderately siderophile elements, tungsten and molybdenum.

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Effects of point source discharges on common bully ( Gobiomorphus cotidianus ) along the Waikato River, New Zealand - David W. West; Nicholas Ling; Brendan J. Hicks; Michael R. van den Heuvel; Louis A. Tremblay (New Zealand Journal of Marine and Freshwater Research, 2022)
The common bully ( Gobiomorphus cotidianus ) was used as a bioindicator to assess the impacts of geothermal, bleached kraft mill effluent (BKME), sewage, and thermal discharges in the Waikato River, Northern New Zealand. A range of morphological and physiological parameters were measured to assess fitness in fish sampled upstream and downstream from these point sources. Isotopic signatures gave evidence that fish were resident at sites and showed a gradient corresponding to site‐specific sources of carbon and nitrogen along the river. There were changes in the size range and age structure of the populations but, no physiological responses were detected. Limited impacts were observed on common bully health at individual discharge sites, or downstream where the river showed gradual deterioration in water quality, particularly nutrient enrichment, and increased turbidity. Despite the gradual deterioration in water quality no concomitant cumulative impacts were observed in common bully. Responses were largely local in nature, responding to point‐source discharges. Population responses at the geothermal and BKME discharge sites warrant further study to investigate possible effects on fish recruitment.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Soil microbial sensitivity to temperature remains unchanged despite community compositional shifts along geothermal gradients - Gabriel Y. K. Moinet; Manpreet K. Dhami; John E. Hunt; Anastasija Podolyan; Liyĭn L. Liáng; Louis A. Schipper; David Whitehead; Jonathan Nuñez; Adriano Nascente; Peter Millard (Global Change Biology, 2021)
Climate warming may be exacerbated if rising temperatures stimulate losses of soil carbon to the atmosphere. The direction and magnitude of this carbon‐climate feedback are uncertain, largely due to lack of knowledge of the thermal adaptation of the physiology and composition of soil microbial communities. Here, we applied the macromolecular rate theory (MMRT) to describe the temperature response of the microbial decomposition of soil organic matter (SOM) in a natural long‐term warming experiment in a geothermally active area in New Zealand. Our objective was to test whether microbial communities adapt to long‐term warming with a shift in their composition and their temperature response that are consistent with evolutionary theory of trade‐offs between enzyme structure and function. We characterized the microbial community composition (using metabarcoding) and the temperature response of microbial decomposition of SOM (using MMRT) of soils sampled along transects of increasing distance from a geothermally active zone comprising two biomes (a shrubland and a grassland) and sampled at two depths (0–50 and 50–100 mm), such that ambient soil temperature and soil carbon concentration varied widely and independently. We found that the different environments were hosting microbial communities with distinct compositions, with thermophile and thermotolerant genera increasing in relative abundance with increasing ambient temperature. However, the ambient temperature had no detectable influence on the MMRT parameters or the relative temperature sensitivity of decomposition ( Q 10 ). MMRT parameters were, however, strongly correlated with soil carbon concentration and carbon:nitrogen ratio. Our findings suggest that, while long‐term warming selects for warm‐adapted taxa, substrate quality and quantity exert a stronger influence than temperature in selecting for distinct thermal traits. The results have major implications for our understanding of the role of soil microbial processes in the long‐term effects of climate warming on soil carbon dynamics and will help increase confidence in carbon‐climate feedback projections.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

High contribution of methane in greenhouse gas emissions from a eutrophic lake: a mass balance synthesis - Arianto B. Santoso; David P. Hamilton; Louis A. Schipper; Ilia S. Ostrovsky; Chris H. Hendy (New Zealand Journal of Marine and Freshwater Research, 2021)
Lakes are ‘hotspots’ for greenhouse gas (GHG) emissions, primarily carbon dioxide (CO 2 ) and methane (CH 4 ). Understanding the processes regulating GHG emissions from lakes, and their temporal variability, is essential for more accurately quantifying the role of lakes in global GHG cycles. In this study, we identified the processes that affect CO 2 and CH 4 concentrations in a small (0.3 km 2 ) eutrophic monomictic lake (Okaro, New Zealand). A mass balance model was used to calculate changes in CO 2 and CH 4 storage in the lake as a result of internal cycling and atmospheric fluxes. To support model computations, CO 2 and CH 4 concentrations profiles were measured monthly over a one‐year period, in addition to temperature, dissolved oxygen and chlorophyll a . Annually, Lake Okaro acted as a sink of CO 2 from the atmosphere (425.4 mmol CO 2 m −2 y −1 ) and a source of CH 4 (553.4 mmol CH 4 m −2 y −1 ) equating to a net GHG emission (diffusive fluxes of CO 2 and CH 4 combined) of 0.22 kg CO 2 ‐eq m −2 y −1 . Although it may be viewed as conservative and applies only to diffusive fluxes, our study indicates that eutrophic lakes with high rates of primary production may act as a net source of GHGs.

SARS-CoV-2 is rapidly inactivated at high temperature - Jennifer Biryukov; Jeremy A. Boydston; Rebecca A. Dunning; John J. Yeager; Stewart Wood; Allison Ferris; David Miller; Wade Weaver; Nathalie E. Zeitouni; Denise Freeburger; Paul Dabisch; Victoria Wahl; et al. (Environmental Chemistry Letters, 2021)
In the absence of a vaccine, preventing the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the primary means to reduce the impact of the 2019 coronavirus disease (COVID-19). Multiple studies have reported the presence of SARS-CoV-2 genetic material on surfaces suggesting that fomite transmission of SARS-CoV-2 is feasible. High temperature inactivation of virus has been previously suggested, but not shown. In the present study, we investigated the environmental stability of SARS-CoV-2 in a clinically relevant matrix dried onto stainless steel at a high temperature. The results show that at 54.5 °C, the virus half-life was 10.8 ± 3.0 min and the time for a 90% decrease in infectivity was 35.4 ± 9.0 min. These findings suggest that in instances where the environment can reach temperatures of at least 54.5 °C, such as in vehicle interior cabins when parked in warmer ambient air, that the potential for exposure to infectious virus on surfaces could be decreased substantially in under an hour.

Phylogeography of a widespread Palaearctic forest bird species: The White‐backed Woodpecker (Aves, Picidae) - Jean‐Marc Pons; David Campión; Giorgio Chiozzi; Antonia Ettwein; Jean‐Louis Grangé; Łukasz Kajtoch; Tomasz D. Mazgajski; Marko Rakovic; Hans Winkler; Jérôme Fuchs (Zoologica Scripta, 2021)
We use multilocus molecular data and species distribution modelling to investigate the phylogenetics and the phylogeography of the White‐backed Woodpecker ( Dendrocopos leucotos ), a bird species widely distributed over the entire Palaearctic. Our phylogenetic results reveal three well‐supported clades within D. leucotos : the Chinese endemic subspecies ( tangi , insularis ), the northerly distributed subspecies ( leucotos , uralensis ) and the four poorly genetically differentiated Japanese subspecies ( subcirris , stejnegeri , namiyei, owstoni ), and the south‐western Palaearctic lilfordi subspecies. According to our results, the Amami Woodpecker, endemic to Amami Oshima Island (Ryukyu archipelago, Japan) sometimes treated as full species Dendrocopos owstoni , does not deserve a species‐level status. Based on the mitochondrial phylogeographic results, the Japanese archipelago was recently colonized only once by D. leucotos from eastern Eurasia. Our results suggest a split between the leucotos and lilfordi lineages that dates back to mid‐Pleistocene (around 0.6 Mya) with likely no gene flow between these two subspecies since then. Our results thus do not support a phylogeographic pattern in which Central Europe and Northern Europe were recolonized from one or several southern glacial refugia where lilfordi populations persisted through several Pleistocene glacial periods. Spatial variation in mitochondrial diversity across leucotos/uralensis populations and niche ecological modelling suggest a possible eastward population expansion from a unique glacial refugium likely located in Central Europe. Molecular species delimitation methods, gene flow analyses and differences in adult and juvenile plumage indicate that the lilfordi subspecies may warrant to be ranked as a valid phylogenetic species. Further studies are nevertheless needed in the Balkans, where leucotos and lilfordi came recently into contact to measure the effectiveness of reproductive barriers and gene flow.

Renal abscess caused by Panton-Valentine leukocidin-producing Staphylococcus aureus : report of an unusual case and review of the literature - Pierre Louis Conan; Isabelle Podglajen; Fabrice Compain; Mehdi Osman; David Lebeaux; Edouard Flamarion (Infectious Diseases, 2021)

Effect of tapping for syrup production on sugar maple tree growth in the Quebec Appalachians - Rock Ouimet; François Guillemette; Louis Duchesne; Jean-David Moore (Trees, 2021)

The missing Myopus : plugging the gaps in Late Pleistocene small mammal identification in western Europe with geometric morphometrics - Louis Arbez; Aurelien Royer; Danielle Schreve; Remi Laffont; Serge David; Sophie Montuire (Journal of Quaternary Science, 2021)
Lemmus and Myopus are two lemming species with distinct habitat requirements but which show very similar dental morphologies. They are thus extremely difficult to distinguish from one another in the fossil record on the basis of their dental remains, leading to poor understanding of the palaeobiogeographical evolution of Myopus as well as inaccurate palaeoenvrionmental reconstructions. Currently, the presence of Myopus in the fossil register from the Pleistocene is still debated and no firm occurrence of this lemming in western Europe has yet been confirmed for the Late Pleistocene. In this paper, we used geometric morphometrics on modern material to establish morphological differences between Lemmus and Myopus teeth (first lower and third upper molars). Morphological data were then used to build a robust linear discriminant model able to confidently classify isolated teeth of these two genera, and finally, linear discriminant models were used on fossil remains of Lemmus/Myopus from two Late Pleistocene archaeological/palaeontological sites (Grotte des Gorges and Gully Cave). This study demonstrates, for the first time, the presence of Myopus schisticolor in west European Late Pleistocene sites between the end of Marine Isotope Stage 3 and the beginning of the Holocene, during climatic events that favoured the development of taiga forest of birch and pine in these regions.

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Chronic cardiac structural damage, diastolic and systolic dysfunction following acute myocardial injury due to bromine exposure in rats - Juan Xavier Masjoan Juncos; Shazia Shakil; Wayne E. Bradley; Chih-Chang Wei; Iram Zafar; Pamela Powell; Nithya Mariappan; William E. Louch; David A. Ford; Aftab Ahmad; Louis J. Dell’Italia; Shama Ahmad (Archives of Toxicology, 2021)

Minnesota landowners’ trust in their department of natural resources, salient values similarity and wildlife value orientations - Larry M. Gigliotti; Lily A. Sweikert; Louis Cornicelli; David C. Fulton (Environment Systems and Decisions, 2020)

An integrated assessment of the potential impacts of climate change on Indiana forests - Richard P. Phillips; Leslie Brandt; P. David Polly; Patrick Zollner; Michael R. Saunders; Keith Clay; Louis Iverson; Songlin Fei (Climatic Change, 2020)

Small strain moduli of compacted silt by ultrasonic pulse velocity measurements - David M. Weidinger; Honghua Zhao; Annie On-Lei Kwok; Xin Kang; Louis Ge (Marine Georesources & Geotechnology, 2020)

Sea-ice and water dynamics and moonlight impact the acoustic backscatter diurnal signal over the eastern Beaufort Sea continental slope - Igor A. Dmitrenko; Vladislav Petrusevich; Gérald Darnis; Sergei A. Kirillov; Alexander S. Komarov; Jens K. Ehn; Alexandre Forest; Louis Fortier; Søren Rysgaard; David G. Barber (Ocean Science, 2020)
A 2-year-long time series of currents and acoustic backscatter from an acoustic Doppler current profiler, moored over the eastern Beaufort Sea continental slope from October 2003 to September 2005, were used to assess the dynamics and variability of the sound-scattering layer. It has been shown that acoustic backscatter is dominated by a synchronized diel vertical migration (DVM) of zooplankton. Our results show that DVM timings (i) were synchronous with sunlight and (ii) were modified by moonlight and sea ice, which attenuates light transmission to the water column. Moreover, DVM is modified or completely disrupted during highly energetic current events. Thicker ice observed during winter–spring 2005 lowered the backscatter values but favored extending DVM toward the midnight sun. In contrast to many previous studies, DVM occurred through the intermediate water layer during the ice-free season of the midnight sun in 2004. In 2005, the midnight-sun DVM was likely impacted by a high acoustic scattering generated by suspended particles. During full moon at low cloud cover, the nighttime moonlight illuminance led to zooplankton avoidance of the subsurface layer, disrupting DVM. Moreover, DVM was disrupted by upwelling, downwelling, and eddy passing. We suggest that these deviations are consistent with DVM adjusting to avoid enhanced water dynamics. For upwelling and downwelling, zooplankton likely respond to the along-slope water dynamics dominated by surface- and depth-intensified flow, respectively. This drives zooplankton to adjust DVM by aggregating in the low or upper intermediate water layer for upwelling and downwelling, respectively. The baroclinic eddy reversed DVM below the eddy core.

The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis - Matthias Albrecht; David Kleijn; Neal M. Williams; Matthias Tschumi; Brett R. Blaauw; Riccardo Bommarco; Alistair J. Campbell; Matteo Dainese; Francis A. Drummond; Martin H. Entling; Dominik Ganser; G. Arjen de Groot; et al. (Ecology Letters, 2020)
Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Micro-solutions to global problems: understanding social processes to eradicate energy poverty and build climate-resilient livelihoods - J David Tàbara; Takeshi Takama; Manisha Mishra; Lauren Hermanus; Sean Khaya Andrew; Pacia Diaz; Gina Ziervogel; Louis Lemkow (Climatic Change, 2020)

β‐Glucan is a major growth substrate for human gut bacteria related to Coprococcus eutactus - Anna M. Alessi; Victoria Gray; Freda M. Farquharson; Adriana Flores‐López; Sophie Shaw; David Stead; Udo Wegmann; Claire Shearman; Mike Gasson; Elaina S. R. Collie‐Duguid; Harry J. Flint; Petra Louis (Environmental Microbiology, 2020)
Summary A clone encoding carboxymethyl cellulase activity was isolated during functional screening of a human gut metagenomic library using Lactococcus lactis MG1363 as heterologous host. The insert carried a glycoside hydrolase family 9 (GH9) catalytic domain with sequence similarity to a gene from Coprococcus eutactus ART55/1. Genome surveys indicated a limited distribution of GH9 domains among dominant human colonic anaerobes. Genomes of C. eutactus ‐related strains harboured two GH9‐encoding and four GH5‐encoding genes, but the strains did not appear to degrade cellulose. Instead, they grew well on β‐glucans and one of the strains also grew on galactomannan, galactan, glucomannan and starch. Coprococcus comes and Coprococcus catus strains did not harbour GH9 genes and were not able to grow on β‐glucans. Gene expression and proteomic analysis of C. eutactus ART55/1 grown on cellobiose, β‐glucan and lichenan revealed similar changes in expression in comparison to glucose. On β‐glucan and lichenan only, one of the four GH5 genes was strongly upregulated. Growth on glucomannan led to a transcriptional response of many genes, in particular a strong upregulation of glycoside hydrolases involved in mannan degradation. Thus, β‐glucans are a major growth substrate for species related to C. eutactus , with glucomannan and galactans alternative substrates for some strains.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

FLEAT: A Multiscale Observational and Modeling Program to Understand How Topography Affects Flows in the Western North Pacific - Shaun Johnston; Martha Schönau; Terri Paluszkiewicz; Jennifer MacKinnon; Brian Arbic; Patrick Colin; Matthew Alford; Magdalena Andres; Luca Centurioni; Hans Graber; Karl Helfrich; Verena Hormann; et al. (Oceanography, 2019)

The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

Staphylococcal driveline infections are the predominant type of left ventricular assist device associated infections in Singapore - Yii Ean Teh; Choon Pin Lim; Louis Loon Yee Teo; Jia Lin Soon; Victor Tar Toong Chao; Chia Lee Neo; Joycelyn Li Li Tan; Ka Lee Kerk; David Kheng Leng Sim; Teing Ee Tan; Ban Hock Tan; Sivathasan Cumaraswamy; et al. (Infectious Diseases, 2019)

The Role of Stakeholders in Creating Societal Value From Coastal and Ocean Observations - Bev Mackenzie; Louis Celliers; Luiz Paulo de Freitas Assad; Johanna J. Heymans; Nicholas Rome; Julie Thomas; Clarissa Anderson; James Behrens; Mark Calverley; Kruti Desai; Paul M. DiGiacomo; Samy Djavidnia; et al. (Frontiers in Marine Science, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

The genomic pool of standing structural variation outnumbers single nucleotide polymorphism by threefold in the marine teleost Chrysophrys auratus - Andrew Catanach; Ross Crowhurst; Cecilia Deng; Charles David; Louis Bernatchez; Maren Wellenreuther (Molecular Ecology, 2019)
Recent studies have highlighted an important role of structural variation (SV) in ecological and evolutionary processes, but few have studied nonmodel species in the wild. As part of our long‐term research programme on the nonmodel teleost fish Australasian snapper ( Chrysophrys auratus ), we aim to build one of the first catalogues of genomic variants (SNPs and indels, and deletions, duplications and inversions) in fishes and evaluate overlap of genomic variants with regions under putative selection (Tajima's D and π ), and coding sequences (genes). For this, we analysed six males and six females from three locations in New Zealand and generated a high‐resolution genomic variation catalogue. We characterized 20,385 SVs and found they intersected with almost a third of all annotated genes. Together with small indels, SVs account for three times more variation in the genome in terms of bases affected compared to SNPs. We found that a sizeable portion of detected SVs was in the upper and lower genomic regions of Tajima's D and π , indicating that some of these have an effect on the phenotype. Together, these results shed light on the often neglected genomic variation that is produced by SVs and highlights the need to go beyond the mere measure of SNPs when investigating evolutionary processes, such as species diversification and adaptation.

Magnetic sensitivity mediated by the Arabidopsis blue-light receptor cryptochrome occurs during flavin reoxidation in the dark - Marootpong Pooam; Louis-David Arthaut; Derek Burdick; Justin Link; Carlos F. Martino; Margaret Ahmad (Planta, 2019)

Less is more: lemurs (Eulemur spp.) may benefit from loss of trichromatic vision - Rachel L. Jacobs; Carrie C. Veilleux; Edward E. Louis; James P. Herrera; Chihiro Hiramatsu; David C. Frankel; Mitchell T. Irwin; Amanda D. Melin; Brenda J. Bradley (Behavioral Ecology and Sociobiology, 2019)

In situ Determination of Nitrate and Hydrogen Sulfide in the Baltic Sea Using an Ultraviolet Spectrophotometer - David Meyer; Ralf D. Prien; Louis Rautmann; Malte Pallentin; Joanna J. Waniek; Detlef E. Schulz-Bull (Frontiers in Marine Science, 2018)

Neural circuits activated by error amplification and haptic guidance training techniques during performance of a timing-based motor task by healthy individuals - Marie-Hélène Milot; Laura Marchal-Crespo; Louis-David Beaulieu; David J. Reinkensmeyer; Steven C. Cramer (Experimental Brain Research, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Climate and soils together regulate photosynthetic carbon isotope discrimination within C 3 plants worldwide - William K. Cornwell; Ian J. Wright; Joel Turner; Vincent Maire; Margaret M. Barbour; Lucas A. Cernusak; Todd Dawson; David Ellsworth; Graham D. Farquhar; Howard Griffiths; Claudia Keitel; Alexander Knohl; et al. (Global Ecology and Biogeography, 2018)
Aim Within C 3 plants, photosynthesis is a balance between CO 2 supply from the atmosphere via stomata and demand by enzymes within chloroplasts. This process is dynamic and a complex but crucial aspect of photosynthesis. We sought to understand the spatial pattern in CO 2 supply–demand balance on a global scale, via analysis of stable isotopes of carbon within leaves (Δ 13 C), which provide an integrative record of CO 2 drawdown during photosynthesis. Location Global Time period 1951–2011. Major taxa studied Vascular plants. Methods We assembled a database of leaf carbon isotope ratios containing 3,979 species–site combinations from across the globe, including 3,645 for C 3 species. We examined a wide array of potential climate and soil drivers of variation in Δ 13 C. Results The strongest drivers of carbon isotope discrimination at the global scale included atmospheric pressure, potential evapotranspiration and soil pH, which explained 44% of the variation in Δ 13 C. Addition of eight more climate and soil variables (each explaining small but highly significant amounts of variation) increased the explained variation to 60%. On top of this, the largest plant trait effect was leaf nitrogen per area, which explained 11% of Δ 13 C variation. Main conclusions: By considering variation in Δ 13 C at a considerably larger scale than previously, we were able to identify and quantify key drivers in CO 2 supply–demand balance previously unacknowledged. Of special note is the key role of soil properties, with greater discrimination on low‐pH and high‐silt soils. Unlike other plant traits, which show typically wide variation within sets of coexisting species, the global pattern in carbon stable isotope ratios is much more conservative; there is relatively narrow variation in time‐integrated CO 2 concentrations at the site of carboxylation among plants in a given soil and climate.

Drought timing and local climate determine the sensitivity of eastern temperate forests to drought - Loïc D'Orangeville; Justin Maxwell; Daniel Kneeshaw; Neil Pederson; Louis Duchesne; Travis Logan; Daniel Houle; Dominique Arseneault; Colin M. Beier; Daniel A. Bishop; Daniel Druckenbrod; Shawn Fraver; et al. (Global Change Biology, 2018)
Projected changes in temperature and drought regime are likely to reduce carbon (C) storage in forests, thereby amplifying rates of climate change. While such reductions are often presumed to be greatest in semi‐arid forests that experience widespread tree mortality, the consequences of drought may also be important in temperate mesic forests of Eastern North America ( ENA ) if tree growth is significantly curtailed by drought. Investigations of the environmental conditions that determine drought sensitivity are critically needed to accurately predict ecosystem feedbacks to climate change. We matched site factors with the growth responses to drought of 10,753 trees across mesic forests of ENA , representing 24 species and 346 stands, to determine the broad‐scale drivers of drought sensitivity for the dominant trees in ENA . Here we show that two factors—the timing of drought, and the atmospheric demand for water (i.e., local potential evapotranspiration; PET )—are stronger drivers of drought sensitivity than soil and stand characteristics. Drought‐induced reductions in tree growth were greatest when the droughts occurred during early‐season peaks in radial growth, especially for trees growing in the warmest, driest regions (i.e., highest PET ). Further, mean species trait values (rooting depth and ψ 50 ) were poor predictors of drought sensitivity, as intraspecific variation in sensitivity was equal to or greater than interspecific variation in 17 of 24 species. From a general circulation model ensemble, we find that future increases in early‐season PET may exacerbate these effects, and potentially offset gains in C uptake and storage in ENA owing to other global change factors.

Variants of the EAAT2 Glutamate Transporter Gene Promoter Are Associated with Cerebral Palsy in Preterm Infants - Shavanthi Rajatileka; David Odd; Matthew T. Robinson; Alexandra C. Spittle; Louis Dwomoh; Maggie Williams; David Harding; Miles Wagstaff; Marie Owen; Charlene Crosby; Jared Ching; Elek Molnár; et al. (Molecular Neurobiology, 2018)

Characteristics of meiofauna in extreme marine ecosystems: a review - Daniela Zeppilli; Daniel Leduc; Christophe Fontanier; Diego Fontaneto; Sandra Fuchs; Andrew J. Gooday; Aurélie Goineau; Jeroen Ingels; Viatcheslav N. Ivanenko; Reinhardt Møbjerg Kristensen; Ricardo Cardoso Neves; Nuria Sanchez; et al. (Marine Biodiversity, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Environmental DNA metabarcoding: Transforming how we survey animal and plant communities - Kristy Deiner; Holly M. Bik; Elvira Mächler; Mathew Seymour; Anaïs Lacoursière‐Roussel; Florian Altermatt; Simon Creer; Iliana Bista; David M. Lodge; Natasha de Vere; Michael E. Pfrender; Louis Bernatchez (Molecular Ecology, 2017)
The genomic revolution has fundamentally changed how we survey biodiversity on earth. High‐throughput sequencing (“ HTS ”) platforms now enable the rapid sequencing of DNA from diverse kinds of environmental samples (termed “environmental DNA ” or “ eDNA ”). Coupling HTS with our ability to associate sequences from eDNA with a taxonomic name is called “ eDNA metabarcoding” and offers a powerful molecular tool capable of noninvasively surveying species richness from many ecosystems. Here, we review the use of eDNA metabarcoding for surveying animal and plant richness, and the challenges in using eDNA approaches to estimate relative abundance. We highlight eDNA applications in freshwater, marine and terrestrial environments, and in this broad context, we distill what is known about the ability of different eDNA sample types to approximate richness in space and across time. We provide guiding questions for study design and discuss the eDNA metabarcoding workflow with a focus on primers and library preparation methods. We additionally discuss important criteria for consideration of bioinformatic filtering of data sets, with recommendations for increasing transparency. Finally, looking to the future, we discuss emerging applications of eDNA metabarcoding in ecology, conservation, invasion biology, biomonitoring, and how eDNA metabarcoding can empower citizen science and biodiversity education.

Spontaneous imbibition of water and determination of effective contact angles in the Eagle Ford Shale Formation using neutron imaging - Victoria H. DiStefano; Michael C. Cheshire; Joanna McFarlane; Lindsay M. Kolbus; Richard E. Hale; Edmund Perfect; Hassina Z. Bilheux; Louis J. Santodonato; Daniel S. Hussey; David L. Jacobson; Jacob M. LaManna; Philip R. Bingham; et al. (Journal of Earth Science, 2017)

Electrospun PLGA Nanofiber Scaffolds Release Ibuprofen Faster and Degrade Slower After In Vivo Implantation - Corinne N. Riggin; Feini Qu; Dong Hwa Kim; Julianne Huegel; David R. Steinberg; Andrew F. Kuntz; Louis J. Soslowsky; Robert L. Mauck; Joseph Bernstein (Annals of Biomedical Engineering, 2017)

Simultaneous Intracranial EEG-fMRI Shows Inter-Modality Correlation in Time-Resolved Connectivity Within Normal Areas but Not Within Epileptic Regions - Ben Ridley; Jonathan Wirsich; Gaelle Bettus; Roman Rodionov; Teresa Murta; Umair Chaudhary; David Carmichael; Rachel Thornton; Serge Vulliemoz; Andrew McEvoy; Fabrice Wendling; Fabrice Bartolomei; et al. (Brain Topography, 2017)

Reconciling seasonal hydraulic risk and plant water use through probabilistic soil–plant dynamics - Xue Feng; Todd E. Dawson; David D. Ackerly; Louis S. Santiago; Sally E. Thompson (Global Change Biology, 2017)
Current models used for predicting vegetation responses to climate change are often guided by the dichotomous needs to resolve either (i) internal plant water status as a proxy for physiological vulnerability or (ii) external water and carbon fluxes and atmospheric feedbacks. Yet, accurate representation of fluxes does not always equate to accurate predictions of vulnerability. We resolve this discrepancy using a hydrodynamic framework that simultaneously tracks plant water status and water uptake. We couple a minimalist plant hydraulics model with a soil moisture model and, for the first time, translate rainfall variability at multiple timescales – with explicit descriptions at daily, seasonal, and interannual timescales – into a physiologically meaningful metric for the risk of hydraulic failure. The model, parameterized with measured traits from chaparral species native to Southern California, shows that apparently similar transpiration patterns throughout the dry season can emerge from disparate plant water potential trajectories, and vice versa. The parsimonious set of parameters that captures the role of many traits across the soil–plant–atmosphere continuum is then used to establish differences in species sensitivities to shifts in seasonal rainfall statistics, showing that co‐occurring species may diverge in their risk of hydraulic failure despite minimal changes to their seasonal water use. The results suggest potential shifts in species composition in this region due to species‐specific changes in hydraulic risk. Our process‐based approach offers a quantitative framework for understanding species sensitivity across multiple timescales of rainfall variability and provides a promising avenue toward incorporating interactions of temporal variability and physiological mechanisms into drought response models.

Carbon dioxide emissions and sediment organic carbon burials across a gradient of trophic state in eleven New Zealand lakes - Arianto B. Santoso; David P. Hamilton; Chris H. Hendy; Louis A. Schipper (Hydrobiologia, 2017)

Autonomous Multi-Platform Observations During the Salinity Processes in the Upper-ocean Regional Study - Eric Lindstrom; Andrey Shcherbina; Luc Rainville; Thomas Farrar; Luca Centurioni; Shenfu Dong; Eric D’Asaro; Charles Eriksen; David Fratantoni; Benjamin Hodges; Verena Hormann; William Kessler; et al. (Oceanography, 2017)

The side of chronic low back pain matters: evidence from the primary motor cortex excitability and the postural adjustments of multifidi muscles - Hugo Massé-Alarie; Louis-David Beaulieu; Richard Preuss; Cyril Schneider (Experimental Brain Research, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Assessment of multi-contaminant exposure in a cancer treatment center: a 2-year monitoring of molds, mycotoxins, endotoxins, and glucans in bioaerosols - Natacha Heutte; Véronique André; Catherine Dubos Arvis; Valérie Bouchart; Françoise Lemarié; Patrick Legendre; Edwige Votier; Marie-Yolande Louis; Stéphane Madelaine; Virginie Séguin; Stéphanie Gente; Philippe Vérité; et al. (Environmental Monitoring and Assessment, 2017)

Bacterial host and reporter gene optimization for genetically encoded whole cell biosensors - Catherine Brutesco; Sandra Prévéral; Camille Escoffier; Elodie C. T. Descamps; Elsa Prudent; Julien Cayron; Louis Dumas; Manon Ricquebourg; Géraldine Adryanczyk-Perrier; Arjan de Groot; Daniel Garcia; Agnès Rodrigue; et al. (Environmental Science and Pollution Research, 2017)

Near‐future pH conditions severely impact calcification, metabolism and the nervous system in the pteropod Heliconoides inflatus - Aurelie Moya; Ella L. Howes; Thomas Lacoue‐Labarthe; Sylvain Forêt; Bishoy Hanna; Mónica Medina; Philip L. Munday; Jue‐Sheng Ong; Jean‐Louis Teyssié; Gergely Torda; Sue‐Ann Watson; David J. Miller; et al. (Global Change Biology, 2016)
Shelled pteropods play key roles in the global carbon cycle and food webs of various ecosystems. Their thin external shell is sensitive to small changes in pH, and shell dissolution has already been observed in areas where aragonite saturation state is ~1. A decline in pteropod abundance has the potential to disrupt trophic networks and directly impact commercial fisheries. Therefore, it is crucial to understand how pteropods will be affected by global environmental change, particularly ocean acidification. In this study, physiological and molecular approaches were used to investigate the response of the Mediterranean pteropod, Heliconoides inflatus , to pH values projected for 2100 under a moderate emissions trajectory ( RCP 6.0). Pteropods were subjected to pH T 7.9 for 3 days, and gene expression levels, calcification and respiration rates were measured relative to pH T 8.1 controls. Gross calcification decreased markedly under low pH conditions, while genes potentially involved in calcification were up‐regulated, reflecting the inability of pteropods to maintain calcification rates. Gene expression data imply that under low pH conditions, both metabolic processes and protein synthesis may be compromised, while genes involved in acid–base regulation were up‐regulated. A large number of genes related to nervous system structure and function were also up‐regulated in the low pH treatment, including a GABA A receptor subunit. This observation is particularly interesting because GABA A receptor disturbances, leading to altered behavior, have been documented in several other marine animals after exposure to elevated CO 2 . The up‐regulation of many genes involved in nervous system function suggests that exposure to low pH could have major effects on pteropod behavior. This study illustrates the power of combining physiological and molecular approaches. It also reveals the importance of behavioral analyses in studies aimed at understanding the impacts of low pH on marine animals.

The Hevea brasiliensis XIP aquaporin subfamily: genomic, structural and functional characterizations with relevance to intensive latex harvesting - David Lopez; Maroua Ben Amira; Daniel Brown; Beatriz Muries; Nicole Brunel-Michac; Sylvain Bourgerie; Benoit Porcheron; Remi Lemoine; Hervé Chrestin; Ewan Mollison; Alessandra Di Cola; Lorenzo Frigerio; et al. (Plant Molecular Biology, 2016)

Plant hydraulic responses to long-term dry season nitrogen deposition alter drought tolerance in a Mediterranean-type ecosystem - Alexandria L. Pivovaroff; Louis S. Santiago; George L. Vourlitis; David A. Grantz; Michael F. Allen (Oecologia, 2016)

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Corticomotor control of lumbar multifidus muscles is impaired in chronic low back pain: concurrent evidence from ultrasound imaging and double-pulse transcranial magnetic stimulation - Hugo Massé-Alarie; Louis-David Beaulieu; Richard Preuss; Cyril Schneider (Experimental Brain Research, 2016)

Model‐specification uncertainty in future forest pest outbreak - Yan Boulanger; David R. Gray; Barry J. Cooke; Louis De Grandpré (Global Change Biology, 2016)
Climate change will modify forest pest outbreak characteristics, although there are disagreements regarding the specifics of these changes. A large part of this variability may be attributed to model specifications. As a case study, we developed a consensus model predicting spruce budworm (SBW, Choristoneura fumiferana [Clem.]) outbreak duration using two different predictor data sets and six different correlative methods. The model was used to project outbreak duration and the uncertainty associated with using different data sets and correlative methods (=model‐specification uncertainty) for 2011–2040, 2041–2070 and 2071–2100, according to three forcing scenarios (RCP 2.6, RCP 4.5 and RCP 8.5). The consensus model showed very high explanatory power and low bias. The model projected a more important northward shift and decrease in outbreak duration under the RCP 8.5 scenario. However, variation in single‐model projections increases with time, making future projections highly uncertain. Notably, the magnitude of the shifts in northward expansion, overall outbreak duration and the patterns of outbreaks duration at the southern edge were highly variable according to the predictor data set and correlative method used. We also demonstrated that variation in forcing scenarios contributed only slightly to the uncertainty of model projections compared with the two sources of model‐specification uncertainty. Our approach helped to quantify model‐specification uncertainty in future forest pest outbreak characteristics. It may contribute to sounder decision‐making by acknowledging the limits of the projections and help to identify areas where model‐specification uncertainty is high. As such, we further stress that this uncertainty should be strongly considered when making forest management plans, notably by adopting adaptive management strategies so as to reduce future risks.

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Climate and human land-use as a driver of Lake Narlay (Eastern France, Jura Mountains) evolution over the last 1200 years: implication for methane cycle - Simon Belle; Valérie Verneaux; Laurent Millet; David Etienne; Andrea Lami; Simona Musazzi; Jean-Louis Reyss; Michel Magny (Journal of Paleolimnology, 2016)

A single regulatory gene is sufficient to alter V ibrio aestuarianus pathogenicity in oysters - David Goudenège; Marie Agnès Travers; Astrid Lemire; Bruno Petton; Philippe Haffner; Yannick Labreuche; Delphine Tourbiez; Sophie Mangenot; Alexandra Calteau; Didier Mazel; Jean Louis Nicolas; Annick Jacq; et al. (Environmental Microbiology, 2015)
Summary Oyster diseases caused by pathogenic vibrios pose a major challenge to the sustainability of oyster farming. In F rance, since 2012 a disease affecting specifically adult oysters has been associated with the presence of V ibrio aestuarianus. Here, by combining genome comparison, phylogenetic analyses and high‐throughput infections of strains isolated before or during the recent outbreaks, we show that virulent strains cluster into two V . aestuarianus lineages independently of the sampling dates. The bacterial lethal dose was not different between strains isolated before or after 2012. Hence, the emergence of a new highly virulent clonal strain is unlikely. Each lineage comprises nearly identical strains, the majority of them being virulent, suggesting that within these phylogenetically coherent virulent lineages a few strains have lost their pathogenicity. Comparative genomics allowed the identification of a single frameshift in a non‐virulent strain. This mutation affects the varS gene that codes for a signal transduction histidine‐protein kinase. Genetic analyses confirmed that varS is necessary for infection of oysters and for a secreted metalloprotease expression. For the first time in a V ibrio species, we show here that VarS is a key factor of pathogenicity.

Global effects of soil and climate on leaf photosynthetic traits and rates - Vincent Maire; Ian J. Wright; I. Colin Prentice; Niels H. Batjes; Radika Bhaskar; Peter M. van Bodegom; Will K. Cornwell; David Ellsworth; Ülo Niinemets; Alejandro Ordonez; Peter B. Reich; Louis S. Santiago (Global Ecology and Biogeography, 2015)
Aim The influence of soil properties on photosynthetic traits in higher plants is poorly quantified in comparison with that of climate. We address this situation by quantifying the unique and joint contributions to global leaf‐trait variation from soils and climate. Location Terrestrial ecosystems world‐wide. Methods Using a trait dataset comprising 1509 species from 288 sites, with climate and soil data derived from global datasets, we quantified the effects of 20 soil and 26 climate variables on light‐saturated photosynthetic rate ( A area ), stomatal conductance ( g s ), leaf nitrogen and phosphorus ( N area and P area ) and specific leaf area ( SLA ) using mixed regression models and multivariate analyses. Results Soil variables were stronger predictors of leaf traits than climatic variables, except for SLA . On average, N area , P area and A area increased and SLA decreased with increasing soil pH and with increasing site aridity. g s declined and P area increased with soil available P ( P avail ). N area was unrelated to total soil N . Joint effects of soil and climate dominated over their unique effects on N area and P area , while unique effects of soils dominated for A area and g s . Path analysis indicated that variation in A area reflected the combined independent influences of N area and g s , the former promoted by high pH and aridity and the latter by low P avail . Main conclusions Three environmental variables were key for explaining variation in leaf traits: soil pH and P avail , and the climatic moisture index (the ratio of precipitation to potential evapotranspiration). Although the reliability of global soil datasets lags behind that of climate datasets, our results nonetheless provide compelling evidence that both can be jointly used in broad‐scale analyses, and that effects uniquely attributable to soil properties are important determinants of leaf photosynthetic traits and rates. A significant future challenge is to better disentangle the covarying physiological, ecological and evolutionary mechanisms that underpin trait–environment relationships.

Climate remains an important driver of post‐European vegetation change in the eastern United States - Neil Pederson; Anthony W. D'Amato; James M. Dyer; David R. Foster; David Goldblum; Justin L. Hart; Amy E. Hessl; Louis R. Iverson; Stephen T. Jackson; Dario Martin‐Benito; Brian C. McCarthy; Ryan W. McEwan; et al. (Global Change Biology, 2015)

Climate‐induced changes in host tree–insect phenology may drive ecological state‐shift in boreal forests - Deepa S. Pureswaran; Louis De Grandpré; David Paré; Anthony Taylor; Martin Barrette; Hubert Morin; Jacques Régnière; Daniel D. Kneeshaw (Ecology, 2015)
Climate change is altering insect disturbance regimes via temperature‐mediated phenological changes and trophic interactions among host trees, herbivorous insects, and their natural enemies in boreal forests. Range expansion and increase in outbreak severity of forest insects are occurring in Europe and North America. The degree to which northern forest ecosystems are resilient to novel disturbance regimes will have direct consequences for the provisioning of goods and services from these forests and for long‐term forest management planning. Among major ecological disturbance agents in the boreal forests of North America is a tortricid moth, the eastern spruce budworm, which defoliates fir ( Abies spp.) and spruce ( Picea spp.). Northern expansion of this defoliator in eastern North America and climate‐induced narrowing of the phenological mismatch between the insect and its secondary host, black spruce ( Picea mariana ), may permit greater defoliation and mortality in extensive northern black spruce forests. Although spruce budworm outbreak centers have appeared in the boreal black spruce zone historically, defoliation and mortality were minor. Potential increases in outbreak severity and tree mortality raise concerns about the future state of this northern ecosystem. Severe spruce budworm outbreaks could decrease stand productivity compared with their occurrence in more diverse, southern balsam fir forest landscapes that have coevolved with outbreaks. Furthermore, depending on the proportion of balsam fir and deciduous species present and fire recurrence, changes in regeneration patterns and in nutrient cycling could alter ecosystem dynamics and replace black spruce by more productive mixed‐wood forest, or by less productive ericaceous shrublands. Long‐term monitoring, manipulative experiments, and process modeling of climate‐induced phenological changes on herbivorous insect pests, their host tree species, and natural enemies in northern forests are therefore crucial to predicting species range shifts and assessing ecological and economic impacts.

Denitrification kinetics in biomass- and biochar-amended soils of different landscape positions - Rajesh Chintala; Rachel K Owen; Thomas E Schumacher; Kurt A Spokas; Louis M McDonald; Sandeep Kumar; David E Clay; Douglas D Malo; Bruce Bleakley (Environmental Science and Pollution Research, 2015)

Isolation of progenitor cells from the blubber of northern elephant seals ( Mirounga angustirostris ) in order to obtain an in vitro adipocyte model—preliminary results - Caroline Louis; Michael S. Tift; Daniel E. Crocker; David Alexander; Donald R. Smith; Cathy Debier (Marine Mammal Science, 2015)

Underworld-GT applied to Guangdong, a tool to explore the geothermal potential of the crust - Steve Quenette; Yufei Xi; John Mansour; Louis Moresi; David Abramson (Journal of Earth Science, 2015)

In silico study of wall-associated kinase family reveals large-scale genomic expansion potentially connected with functional diversification in Populus - Kévin Tocquard; Clément Lafon-Placette; Daniel Auguin; Beatriz Muries; Gisèle Bronner; David Lopez; Boris Fumanal; Jérôme Franchel; Sylvain Bourgerie; Stéphane Maury; Philippe Label; Jean-Louis Julien; et al. (Tree Genetics & Genomes, 2014)

Rapid changes in growth, condition, size and age of small pelagic fish in the Mediterranean - Elisabeth Van Beveren; Sylvain Bonhommeau; Jean-Marc Fromentin; Jean-Louis Bigot; Jean-Hervé Bourdeix; Pablo Brosset; David Roos; Claire Saraux (Marine Biology, 2014)

A derivative-free methodology with local and global search for the constrained joint optimization of well locations and controls - Obiajulu J. Isebor; Louis J. Durlofsky; David Echeverría Ciaurri (Computational Geosciences, 2014)

How do various maize crop models vary in their responses to climate change factors? - Simona Bassu; Nadine Brisson; Jean‐Louis Durand; Kenneth Boote; Jon Lizaso; James W. Jones; Cynthia Rosenzweig; Alex C. Ruane; Myriam Adam; Christian Baron; Bruno Basso; Christian Biernath; et al. (Global Change Biology, 2014)
Potential consequences of climate change on crop production can be studied using mechanistic crop simulation models. While a broad variety of maize simulation models exist, it is not known whether different models diverge on grain yield responses to changes in climatic factors, or whether they agree in their general trends related to phenology, growth, and yield. With the goal of analyzing the sensitivity of simulated yields to changes in temperature and atmospheric carbon dioxide concentrations [ CO 2 ], we present the largest maize crop model intercomparison to date, including 23 different models. These models were evaluated for four locations representing a wide range of maize production conditions in the world: Lusignan (France), Ames ( USA ), Rio Verde (Brazil) and Morogoro (Tanzania). While individual models differed considerably in absolute yield simulation at the four sites, an ensemble of a minimum number of models was able to simulate absolute yields accurately at the four sites even with low data for calibration, thus suggesting that using an ensemble of models has merit. Temperature increase had strong negative influence on modeled yield response of roughly −0.5 Mg ha −1 per °C. Doubling [ CO 2 ] from 360 to 720 μmol mol −1 increased grain yield by 7.5% on average across models and the sites. That would therefore make temperature the main factor altering maize yields at the end of this century. Furthermore, there was a large uncertainty in the yield response to [ CO 2 ] among models. Model responses to temperature and [ CO 2 ] did not differ whether models were simulated with low calibration information or, simulated with high level of calibration information.

PDGFB Partial Deletion: a New, Rare Mechanism Causing Brain Calcification with Leukoencephalopathy - Gaël Nicolas; Anne Rovelet-Lecrux; Cyril Pottier; Olivier Martinaud; David Wallon; Louis Vernier; Gérard Landemore; Françoise Chapon; Carol Prieto-Morin; Elisabeth Tournier-Lasserve; Thierry Frébourg; Dominique Campion; et al. (Journal of Molecular Neuroscience, 2014)

The effect of cognitive task complexity on gait stability in adolescents following concussion - David R. Howell; Louis R. Osternig; Michael C. Koester; Li-Shan Chou (Experimental Brain Research, 2014)

Nutritional models of foetal programming and nutrigenomic and epigenomic dysregulations of fatty acid metabolism in the liver and heart - Jean-Louis Guéant; Rania Elakoum; Olivier Ziegler; David Coelho; Eva Feigerlova; Jean-Luc Daval; Rosa-Maria Guéant-Rodriguez (Pflügers Archiv - European Journal of Physiology, 2014)

A Nanoengineered Embolic Agent for Precise Radiofrequency Ablation - Pierre Henri Rolland; Joel L. Berry; Guillaume Louis; Lionel Velly; Vincent Vidal; Pauline Brige; Vinuta Mayakonda; David L. Carroll (Annals of Biomedical Engineering, 2014)

The Tendon Injury Response is Influenced by Decorin and Biglycan - Andrew A. Dunkman; Mark R. Buckley; Michael J. Mienaltowski; Sheila M. Adams; Stephen J. Thomas; Lauren Satchell; Akash Kumar; Lydia Pathmanathan; David P. Beason; Renato V. Iozzo; David E. Birk; Louis J. Soslowsky (Annals of Biomedical Engineering, 2014)

Genome-wide association study and meta-analysis of intraocular pressure - A. Bilge Ozel; Sayoko E. Moroi; David M. Reed; Melisa Nika; Caroline M. Schmidt; Sara Akbari; Kathleen Scott; Frank Rozsa; Hemant Pawar; David C. Musch; Paul R. Lichter; Doug Gaasterland; et al. (Human Genetics, 2014)

Generalized Spike and Waves: Effect of Discharge Duration on Brain Networks as Revealed by BOLD fMRI - Matteo Pugnaghi; David W. Carmichael; Anna E. Vaudano; Umair J. Chaudhary; Francesca Benuzzi; Carlo Di Bonaventura; Anna T. Giallonardo; Roman Rodionov; Matthew C. Walker; John S. Duncan; Stefano Meletti; Louis Lemieux (Brain Topography, 2014)

Large trees drive forest aboveground biomass variation in moist lowland forests across the tropics - J. W. Ferry Slik; Gary Paoli; Krista McGuire; Ieda Amaral; Jorcely Barroso; Meredith Bastian; Lilian Blanc; Frans Bongers; Patrick Boundja; Connie Clark; Murray Collins; Gilles Dauby; et al. (Global Ecology and Biogeography, 2013)
Aim Large trees (d.b.h. ≥ 70 cm) store large amounts of biomass. Several studies suggest that large trees may be vulnerable to changing climate, potentially leading to declining forest biomass storage. Here we determine the importance of large trees for tropical forest biomass storage and explore which intrinsic (species trait) and extrinsic (environment) variables are associated with the density of large trees and forest biomass at continental and pan‐tropical scales. Location Pan‐tropical. Methods Aboveground biomass ( AGB) was calculated for 120 intact lowland moist forest locations. Linear regression was used to calculate variation in AGB explained by the density of large trees. Akaike information criterion weights ( AICc ‐wi) were used to calculate averaged correlation coefficients for all possible multiple regression models between AGB /density of large trees and environmental and species trait variables correcting for spatial autocorrelation. Results Density of large trees explained c . 70% of the variation in pan‐tropical AGB and was also responsible for significantly lower AGB in Neotropical [287.8 (mean) ± 105.0 ( SD ) M g ha −1 ] versus Palaeotropical forests (Africa 418.3 ± 91.8 M g ha −1 ; Asia 393.3 ± 109.3 M g ha −1 ). Pan‐tropical variation in density of large trees and AGB was associated with soil coarseness (negative), soil fertility (positive), community wood density (positive) and dominance of wind dispersed species (positive), temperature in the coldest month (negative), temperature in the warmest month (negative) and rainfall in the wettest month (positive), but results were not always consistent among continents. Main conclusions Density of large trees and AGB were significantly associated with climatic variables, indicating that climate change will affect tropical forest biomass storage. Species trait composition will interact with these future biomass changes as they are also affected by a warmer climate. Given the importance of large trees for variation in AGB across the tropics, and their sensitivity to climate change, we emphasize the need for in‐depth analyses of the community dynamics of large trees.

Analysis of carbohydrate storage granules in the diazotrophic cyanobacterium Cyanothece sp. PCC 7822 - David G. Welkie; Debra M. Sherman; William B. Chrisler; Galya Orr; Louis A. Sherman (Photosynthesis Research, 2013)

Cyclooxygenase-2 positively regulates Akt signalling and enhances survival of erythroleukemia cells exposed to anticancer agents - Julian Bertrand; Bertrand Liagre; Lamia Ghezali; Jean-Louis Beneytout; David Yannick Leger (Apoptosis, 2013)

Weak divergence among African, Malagasy and Seychellois hinged terrapins (Pelusios castanoides, P. subniger) and evidence for human-mediated oversea dispersal - Uwe Fritz; William R. Branch; Philip-Sebastian Gehring; James Harvey; Carolin Kindler; Leon Meyer; Louis Du Preez; Pavel Široký; David R. Vieites; Miguel Vences (Organisms Diversity & Evolution, 2013)

Biological invasions in soil: DNA barcoding as a monitoring tool in a multiple taxa survey targeting European earthworms and springtails in North America - David Porco; Thibaud Decaëns; Louis Deharveng; Samuel W. James; Dariusz Skarżyński; Christer Erséus; Kevin R. Butt; Benoit Richard; Paul D. N. Hebert (Biological Invasions, 2013)

Spatial and temporal trends in water quality in a Mediterranean temporary river impacted by sewage effluents - Arthur David; Marie-George Tournoud; Jean-Louis Perrin; David Rosain; Claire Rodier; Christian Salles; Chrystelle Bancon-Montigny; Bernadette Picot (Environmental Monitoring and Assessment, 2013)

Influence of sample location and livestock numbers on Sporormiella concentrations and accumulation rates in surface sediments of Lake Allos, French Alps - David Etienne; Bruno Wilhelm; Pierre Sabatier; Jean-Louis Reyss; Fabien Arnaud (Journal of Paleolimnology, 2013)

Phenotypic Effects of Cattle Mitochondrial DNA in American Bison - James N. Derr; Philip W. Hedrick; Natalie D. Halbert; Louis Plough; Lauren K. Dobson; Julie King; Calvin Duncan; David L. Hunter; Noah D. Cohen; Dennis Hedgecock (Conservation Biology, 2012)
Hybridization between endangered species and more common species is a significant problem in conservation biology because it may result in extinction or loss of adaptation. The historical reduction in abundance and geographic distribution of the American plains bison (Bison bison bison) and their recovery over the last 125 years is well documented. However, introgression from domestic cattle (Bos taurus) into the few remaining bison populations that existed in the late 1800s has now been identified in many modern bison herds. We examined the phenotypic effect of this ancestry by comparing weight and height of bison with cattle or bison mitochondrial DNA (mtDNA) from Santa Catalina Island, California (U.S.A.), a nutritionally stressful environment for bison, and of a group of age‐matched feedlot bison males in Montana, a nutritionally rich environment. The environmental and nutritional differences between these 2 bison populations were very different and demonstrated the phenotypic effect of domestic cattle mtDNA in bison over a broad range of conditions. For example, the average weight of feedlot males that were 2 years of age was 2.54 times greater than that of males from Santa Catalina Island. In both environments, bison with cattle mtDNA had lower weight compared with bison with bison mtDNA, and on Santa Catalina Island, the height of bison with cattle mtDNA was lower than the height of bison with bison mtDNA. These data support the hypothesis that body size is smaller and height is lower in bison with domestic cattle mtDNA and that genomic integrity is important for the conservation of the American plains bison . Efectos Fenotípicos del ADN Mitocondrial de Ganado en el Bisonte Americano

Taxonomic and functional characterization of microbial communities in Technosols constructed for remediation of a contaminated industrial wasteland - Farhan Hafeez; Fabrice Martin-Laurent; Jérémie Béguet; David Bru; Jérôme Cortet; Christophe Schwartz; Jean-Louis Morel; Laurent Philippot (Journal of Soils and Sediments, 2012)

Joint optimization of oil well placement and controls - Mathias C. Bellout; David Echeverría Ciaurri; Louis J. Durlofsky; Bjarne Foss; Jon Kleppe (Computational Geosciences, 2012)

Grass competition is more important than seed ingestion by livestock for Acacia recruitment in South Africa - Séraphine Grellier; Sébastien Barot; Jean-Louis Janeau; David Ward (Plant Ecology, 2012)

Size-dependent behavior of tuna in an array of fish aggregating devices (FADs) - Marianne Robert; Laurent Dagorn; Jean Louis Deneubourg; David Itano; Kim Holland (Marine Biology, 2012)

Implication of two in-stream processes in the fate of nutrients discharged by sewage system into a temporary river - Arthur David; Jean-Louis Perrin; David Rosain; Claire Rodier; Bernadette Picot; Marie-George Tournoud (Environmental Monitoring and Assessment, 2011)

Mechanical, Compositional, and Structural Properties of the Post-natal Mouse Achilles Tendon - Heather L. Ansorge; Sheila Adams; David E. Birk; Louis J. Soslowsky (Annals of Biomedical Engineering, 2011)

Denitrification Potential in Lake Sediment Increases Across a Gradient of Catchment Agriculture - Denise A. Bruesewitz; David P. Hamilton; Louis A. Schipper (Ecosystems, 2011)

Within-season temporal variation in correlations between vineyard canopy and winegrape composition and yield - Andrew Hall; David W. Lamb; Bruno P. Holzapfel; John P. Louis (Precision Agriculture, 2011)

Photodegradation leads to increased carbon dioxide losses from terrestrial organic matter - SUSANNA RUTLEDGE; DAVID I. CAMPBELL; DENNIS BALDOCCHI; LOUIS A. SCHIPPER (Global Change Biology, 2010)
CO 2 production in terrestrial ecosystems is generally assumed to be solely biologically driven while the role of abiotic processes has been largely overlooked. In addition to microbial decomposition, photodegradation – the direct breakdown of organic matter (OM) by solar irradiance – has been found to contribute to litter mass loss in dry ecosystems. Previous small‐scale studies have shown that litter degradation by irradiance is accompanied by emissions of CO 2 . However, the contribution of photodegradation to total CO 2 losses at ecosystems scales is unknown. This study determined the proportion of the total CO 2 losses caused by photodegradation in two ecosystems: a bare peatland in New Zealand and a seasonally dry grassland in California. The direct effect of solar irradiance on CO 2 production was examined by comparing daytime CO 2 fluxes measured using eddy covariance (EC) systems with simultaneous measurements made using an opaque chamber and the soil CO 2 gradient technique, and with night‐time EC measurements under the same soil temperature and moisture conditions. In addition, a transparent chamber was used to directly measure CO 2 fluxes from OM caused by solar irradiance. Photodegradation contributed 19% of the annual CO 2 flux from the peatland and almost 60% of the dry season CO 2 flux from the grassland, and up to 62% and 92% of the summer mid‐day CO 2 fluxes, respectively. Our results suggest that photodegradation may be important in a wide range of ecosystems with exposed OM. Furthermore, the practice of partitioning daytime ecosystem CO 2 exchange into its gross components by assuming that total daytime CO 2 losses can be approximated using estimates of biological respiration alone may be in error. To obtain robust estimates of global ecosystem–atmosphere carbon transfers, the contribution of photodegradation to OM decomposition must be quantified for other ecosystems and the results incorporated into coupled carbon–climate models.

Rotating spatial harvests and fishing effort displacement: a comment on Game et al. (2009) - David M. Kaplan; Deborah R. Hart; Louis W. Botsford (Ecology Letters, 2010)
Ecology Letters (2010) 13: E10–E12 Abstract Game et al. (2009) explored using rapid rotational fishing for increasing herbivore biomass. Their results depend crucially on the assumption that fishing effort that was in closures disappears, rather than shifting elsewhere. If effort shifts, rapid rotation has no effects, but previous age‐structured analyses show benefits of longer period rotation that are robust to effort displacement.

NeuroAIDS in Africa - Kevin Robertson; Jeff Liner; James Hakim; Jean-Louis Sankalé; Igor Grant; Scott Letendre; David Clifford; Amadou Gallo Diop; Assan Jaye; Georgette Kanmogne; Alfred Njamnshi; T. Dianne Langford; et al. (Journal of NeuroVirology, 2010)

Ten Putative Contributors to the Obesity Epidemic - Emily J. McAllister; Nikhil V. Dhurandhar; Scott W. Keith; Louis J. Aronne; Jamie Barger; Monica Baskin; Ruth M. Benca; Joseph Biggio; Mary M. Boggiano; Joe C. Eisenmann; Mai Elobeid; Kevin R. Fontaine; et al. (Critical Reviews in Food Science and Nutrition, 2009)

Relationships Between Total and Non-Recoverable Strain Fields in Glenohumeral Capsule During Shoulder Subluxation - David M. Malicky; Louis J. Soslowsky (Annals of Biomedical Engineering, 2009)

Community hunting in logging concessions: towards a management model for Cameroon’s dense forests - Cédric Vermeulen; Cecilia Julve; Jean-Louis Doucet; David Monticelli (Biodiversity and Conservation, 2009)

An Overview of Global Observing Systems Relevant to GODAE - Candyce Clark; D.E. Harrison; Mike Johnson; Graeme Ball; Howard Freeland; Gustavo Goni; Maria Hood; Michael McPhaden; David Meldrum; Mark Merrifield; Dean Roemmich; Chris Sabine; et al. (Oceanography, 2009)

Phylogeny of Collembola based on cuticular compounds:inherent usefulness and limitation of a character type - David Porco; Louis Deharveng (The Science of Nature, 2009)

Plant water parameters and the remote sensing R 1300/R 1450 leaf water index: controlled condition dynamics during the development of water deficit stress - Hans-Dieter Seelig; Alexander Hoehn; Louis S. Stodieck; David M. Klaus; William W. Adams; William J. Emery (Irrigation Science, 2009)

GABA-B1 Receptors are Coupled to the ERK1/2 MAP Kinase Pathway in the Absence of GABA-B2 Subunits - Maxime Richer; Martin David; Louis R. Villeneuve; Phan Trieu; Nathalie Ethier; Darlaine Pétrin; Aida M. Mamarbachi; Terence E. Hébert (Journal of Molecular Neuroscience, 2009)

Theoretical analysis of reverse-time correlation for idealized orientation tuning dynamics - Gregor Kovačič; Louis Tao; David Cai; Michael J. Shelley (Journal of Computational Neuroscience, 2008)

Nutrient constraints to tropical agroecosystem productivity in long‐term degrading soils - SOLOMON NGOZE; SUSAN RIHA; JOHANNES LEHMANN; LOUIS VERCHOT; JAMES KINYANGI; DAVID MBUGUA; ALICE PELL (Global Change Biology, 2008)
Soil degradation is one of the most serious threats to sustainable crop production in many tropical agroecosystems where extensification rather than intensification of agriculture has occurred. In the highlands of western Kenya, we investigated soil nitrogen (N) and phosphorus (P) constraints to maize productivity across a cultivation chronosequence in which land‐use history ranged from recent conversion from primary forest to 100 years in continuous cropping. Nutrient treatments included a range of N and P fertilizer rates applied separately and in combination. Maize productivity without fertilizer was used as a proxy measure for indigenous soil fertility (ISF). Soil pools of mineral nitrogen, strongly bound P and plant‐available P decreased by 82%, 31% and 36%, and P adsorption capacity increased by 51% after 100 years of continuous cultivation. For the long rainy season (LR), grain yield without fertilizer declined rapidly as cultivation age increased from 0 to 25 years and then gradually declined to a yield of 1.6 Mg ha −1 , which was maintained as time under cultivation increased from 60 to 100 years. LR grain yield in the old conversions was only 24% of the average young conversion grain yield (6.4 Mg ha −1 ). Application of either N or P alone significantly increased grain yield in both the LR and short rainy (SR) seasons, but only application of 120 kg N ha −1 on the old conversion increased yield by >1 Mg ha −1 . In both SR and LR, there was a greater average yield increment response to N and P when applied together (ranging from 1 to 3.8 Mg ha −1 for the LR), with the greatest responses on the old conversions. The benefit–cost ratio (BCR) for applying 120 kg N ha −1 alone was 1 for applying 25 kg P ha −1 alone at all levels of conversion for both seasons. Application of both N (120 kg N ha −1 ) and P (25 kg P ha −1 ) on the old conversions resulted in the greatest BCRs. This study clearly indicates that maize productivity responses to N and P fertilizer are significantly affected by the age of cultivation and its influence on ISF, but that loss of productivity can be restored rapidly when these limiting nutrients are applied. Management strategies should consider ISF and economic factors to determine optimal N and P input requirements for achieving and sustaining profitable crop production on degraded soils.

Divergent abdominal bristle patterns in two distantly related drosophilids: antero-posterior variations and sexual dimorphism in a modular trait - Luciana O. Araripe; Amir Yassin; Louis Bernard Klaczko; Brigitte Moréteau; Jean R. David (Genetica, 2008)

Plant species traits are the predominant control on litter decomposition rates within biomes worldwide - William K. Cornwell; Johannes H. C. Cornelissen; Kathryn Amatangelo; Ellen Dorrepaal; Valerie T. Eviner; Oscar Godoy; Sarah E. Hobbie; Bart Hoorens; Hiroko Kurokawa; Natalia Pérez‐Harguindeguy; Helen M. Quested; Louis S. Santiago; et al. (Ecology Letters, 2008)
Worldwide decomposition rates depend both on climate and the legacy of plant functional traits as litter quality. To quantify the degree to which functional differentiation among species affects their litter decomposition rates, we brought together leaf trait and litter mass loss data for 818 species from 66 decomposition experiments on six continents. We show that: (i) the magnitude of species‐driven differences is much larger than previously thought and greater than climate‐driven variation; (ii) the decomposability of a species’ litter is consistently correlated with that species’ ecological strategy within different ecosystems globally, representing a new connection between whole plant carbon strategy and biogeochemical cycling. This connection between plant strategies and decomposability is crucial for both understanding vegetation–soil feedbacks, and for improving forecasts of the global carbon cycle.

Extraneous variables and their influence on reflectance-based measurements of leaf water content - Hans-Dieter Seelig; William W. Adams; Alexander Hoehn; Louis S. Stodieck; David M. Klaus; William J. Emery (Irrigation Science, 2008)

The implication of life style on codon usage patterns and predicted highly expressed genes for three Frankia genomes - Arnab Sen; Saubashya Sur; Asim K. Bothra; David R. Benson; Philippe Normand; Louis S. Tisa (Antonie van Leeuwenhoek, 2008)

Diversity of Predominant Lactic Acid Bacteria Associated with Cocoa Fermentation in Nigeria - Melanie Kostinek; Louis Ban-Koffi; Margaret Ottah-Atikpo; David Teniola; Ulrich Schillinger; Wilhelm H. Holzapfel; Charles M. A. P. Franz (Current Microbiology, 2008)

The effects of cyclic dynamics and mating system on the effective size of an island mouflon population - RENAUD KAEUFFER; DAVID W. COLTMAN; JEAN‐LOUIS CHAPUIS; DENIS RÉALE; DOMINIQUE PONTIER (Molecular Ecology, 2007)
The Haute Island mouflon ( Ovis aries ) population is isolated on one small (6.5 km 2 ) island of the remote Kerguelen archipelago. Given a promiscuous mating system, a cyclic demography and a strong female‐biased sex ratio after population crashes, we expected a low effective population size ( N e ). We estimated N e using demographic and temporal genetic approaches based on genetic information at 25 microsatellite loci from 62 and 58 mouflons sampled in 1988 and 2003, respectively. Genetic N e estimates were higher than expected, varying between 104 and 250 depending on the methods used. Both demographic and genetic approaches show the Haute Island N e is buffered against population crashes. The unexpectedly high N e likely results from the cyclic winter crashes that allow young males to reproduce, limiting the variance of male reproductive success. Based on individual‐based simulations, we suggest that despite a strongly female‐biased sex ratio, the effects of the mating system on the effective population size more closely resemble random mating or weak polygyny.

Inversion polymorphism and a new polytene chromosome map of Zaprionus indianus Gupta (1970) (Diptera: drosophilidae) - Galina Ananina; Cláudia Rohde; Jean R. David; Vera L. S. Valente; Louis B. Klaczko (Genetica, 2007)

Genetic evidence for kin aggregation in the intertidal acorn barnacle ( Semibalanus balanoides ) - DAVID VELIZ; PIERRE DUCHESNE; EDWIN BOURGET; LOUIS BERNATCHEZ (Molecular Ecology, 2006)
It is generally assumed that larvae of benthic species are thoroughly mixed in the plankton and distributed randomly at settlement. Yet, it has also been hypothesized that a combination of larval gregarious behaviour coupled with particular oceanographic conditions may prevent larvae from mixing completely, and result in nonrandom spatial distributions following settlement. Using microsatellite markers, the main objective of this study was to investigate the occurrence of statistical connections between relatedness and settlement in the intertidal acorn barnacle from the Gulf of St Lawrence, Canada. A second objective was to test the hypothesis that patches of kin‐related individuals came from a common parental site. Our results indicated that a significant number of barnacles within a given sample were more closely related than expected by chance despite the enormous potential for admixture during the planktonic phase. Thus, eight out of 37 samples analysed had relatedness values significantly higher than expected from random settlement. Moreover, analyses of sibship network construction and network complexity tests provided evidence for the occurrence of networks within several samples that were characterized by strong connections among individuals. Thus, nonrandom planktonic dispersal associated with relatively stable oceanic currents, as well as additional ecological factors to be rigorously investigated (e.g. behavioural mechanisms), may be more important in determining patterns of genetic structure in marine benthic invertebrates than generally assumed. Therefore, documenting genetic patterns associated with kin aggregation should be a fruitful and an important avenue for future studies in marine invertebrates.

Sexual dimorphism of body size and sternopleural bristle number: a comparison of geographic populations of an invasive cosmopolitan drosophilid - Jean R. David; Luciana O. Araripe; Blanche C. Bitner-Mathé; Pierre Capy; Beatriz Goñi; Louis Bernard Klaczko; Hélène Legout; Marlucia B. Martins; Joseph Vouidibio; Amir Yassin; Brigitte Moreteau (Genetica, 2006)

Genetic identification of units for conservation in tomato frogs, genus Dyscophus - Ylenia Chiari; Pablo Orozco-terWengel; Miguel Vences; David R. Vieites; Augustin Sarovy; Jasmin E. Randrianirina; Axel Meyer; Edward Louis (Conservation Genetics, 2006)

Intercellular adhesion molecule-1 and childhood asthma - Yu-Fen Li; Yo-Hsuang Tsao; W. James Gauderman; David V. Conti; Edward Avol; Louis Dubeau; Frank D. Gilliland (Human Genetics, 2005)

Molecular and genealogical characterization of the R1443X BRCA1 mutation in high-risk French-Canadian breast/ovarian cancer families - Hélène Vézina; Francine Durocher; Martine Dumont; Louis Houde; Csilla Szabo; Martine Tranchant; Jocelyne Chiquette; Marie Plante; Rachel Laframboise; Jean Lépine; Heli Nevanlinna; Dominique Stoppa-Lyonnet; et al. (Human Genetics, 2005)

Carbon exchange of grazed pasture on a drained peat soil - Joost P. Nieveen; David I. Campbell; Louis A. Schipper; Ian J. Blair (Global Change Biology, 2005)
Land‐use changes have contributed to increased atmospheric CO 2 concentrations. Conversion from natural peatlands to agricultural land has led to widespread subsidence of the peat surface caused by soil compaction and mineralization. To study the net ecosystem exchange of carbon (C) and the contribution of respiration to peat subsidence, eddy covariance measurements were made over pasture on a well‐developed, drained peat soil from 22 May 2002 to 21 May 2003. The depth to the water table fluctuated between 0.02 m in winter 2002 to 0.75 m during late summer and early autumn 2003. Peat soil moisture content varied between 0.6 and 0.7 m 3 m −3 until the water table dropped below 0.5 m, when moisture content reached 0.38 m 3 m −3 . Neither depth to water table nor soil moisture was found to have an effect on the rate of night‐time respiration (ranging from 0.4–8.0 μmol CO 2 m −2 s −1 in winter and summer, respectively). Most of the variance in night‐time respiration was explained by changes in the 0.1 m soil temperature ( r 2 =0.93). The highest values for daytime net ecosystem exchange were measured in September 2002, with a maximum of −17.2 μmol CO 2 m −2 s −1 . Grazing events and soil moisture deficiencies during a short period in summer reduced net CO 2 exchange. To establish an annual C balance for this ecosystem, non‐linear regression was used to model missing data. Annually integrated (CO 2 ) C exchange for this peat–pasture ecosystem was 45±500 kg C ha −1 yr −1 . After including other C exchanges (methane emissions from cows and production of milk), the net annual C loss was 1061±500 kg C ha −1 yr −1 .

Deletion of the endothelin-A receptor gene within the developing mandible - Louis-Bruno Ruest; Rafal Kedzierski; Masashi Yanagisawa; David E. Clouthier (Cell and Tissue Research, 2005)

Rewarding effects elicited by cocaine microinjections into the ventral tegmental area of C57BL/6 mice: involvement of dopamine D1 and serotonin1B receptors - Vincent David; Louis Segu; Marie-Christine Buhot; Marina Ichaye; Pierre Cazala (Psychopharmacology, 2004)

Occurrence and distribution of Vibrio cholerae in the coastal environment of Peru - Ana I. Gil; Valérie R. Louis; Irma N. G. Rivera; Erin Lipp; Anwar Huq; Claudio F. Lanata; David N. Taylor; Estelle Russek‐Cohen; Nipa Choopun; R. Bradley Sack; Rita R. Colwell (Environmental Microbiology, 2004)
Summary The occurrence and distribution of Vibrio cholerae in sea water and plankton along the coast of Peru were studied from October 1997 to June 2000, and included the 1997–98 El Niño event. Samples were collected at four sites in coastal waters off Peru at monthly intervals. Of 178 samples collected and tested, V. cholerae O1 was cultured from 10 (5.6%) samples, and V. cholerae O1 was detected by direct fluorescent antibody assay in 26 out of 159 samples tested (16.4%). Based on the number of cholera cases reported in Peru from 1997 to 2000, a significant correlation was observed between cholera incidence and elevated sea surface temperature (SST) along the coast of Peru ( P V. cholerae in Peru. The climate–cholera relationship observed for the 1997–98 El Niño year suggests that an early warning system for cholera risk can be established for Peru and neighbouring Latin American countries.

Annual and seasonal habitat use of Columbian black-tailed deer in urban Vancouver, Washington - Louis C. Bender; David P. Anderson; Jeffrey C. Lewis (Urban Ecosystems, 2004)

Trends in tree growth and understory yield in silvopastoral practices with southern pines - Adrian Ares; David St. Louis; David Brauer (Agroforestry Systems, 2003)

AFLP utility for population assignment studies: analytical investigation and empirical comparison with microsatellites - David Campbell; Pierre Duchesne; Louis Bernatchez (Molecular Ecology, 2003)
Individual‐based population assignment tests have thus far mainly relied on the use of microsatellite loci. However, the logistic difficulty of screening large numbers of loci required to reach sufficient statistical power hampers the usefulness of microsatellites in situations of weak population structuring. Amplified fragment length polymorphisms (AFLP) represents an alternative for overcoming this logistical issue as the technique allows the user to characterize a much larger number of loci with a comparable analytical effort. In this study, an assignment test based on maximum likelihood for dominant markers was used to investigate the potential usefulness of AFLP for population assignment. We also compared assignment success achieved with AFLP with that obtained using microsatellites in a case study of low population differentiation involving whitefish ( Coregonus clupeaformis ) sympatric ecotypes. The analytical investigation showed that the minimum number of AFLP loci required to reach an assignment success of 95% stood within values that are easily achievable in many situations. This also showed how assignment success varied according to the number of AFLP loci used, their absolute frequency and their frequency differential and sampling errors, as well as the number of putative source populations. The case study showed that given a comparable analytical effort in the laboratory, AFLP were much more efficient than the microsatellite loci in discriminating the source of an individual among putative populations. AFLP resulted in higher assignment success at all levels of stringency and the log‐likelihood differences between populations obtained with AFLP for each individual were much larger than those obtained with microsatellites. These results indicate that research involving individual‐based population assignment methods should benefit importantly from the use of AFLP markers, especially in systems characterized by weak population structuring.

The circumsphere as a tool to assess distortion in [4Fe-4S] atom clusters - James A. Fee; Jesus M. Castagnetto; David A. Case; Louis Noodleman; C. David Stout; Rhonda A. Torres (JBIC Journal of Biological Inorganic Chemistry, 2003)

Effects of dexfenfluramine on aristolochic acid nephrotoxicity in a rat model for Chinese-herb nephropathy - Frédéric Debelle; Joëlle Nortier; Volker M. Arlt; Eric De Prez; Anne Vienne; Isabelle Salmon; David H. Phillips; Monique Deschodt-Lanckman; Jean-Louis Vanherweghem (Archives of Toxicology, 2003)

Female brown-headed cowbirds' (Molothrus ater) social assortment changes in response to male song: a potential source of public information - Julie Gros-Louis; David J. White; Andrew P. King; Meredith J. West (Behavioral Ecology and Sociobiology, 2003)

FeMo cofactor of nitrogenase: energetics and local interactions in the protein environment - Timothy Lovell; Jian Li; David A. Case; Louis Noodleman (JBIC Journal of Biological Inorganic Chemistry, 2002)

Rotator Cuff Tendinosis in an Animal Model: Role of Extrinsic and Overuse Factors - Louis J. Soslowsky; Stavros Thomopoulos; Adil Esmail; Colleen L. Flanagan; Joseph P. Iannotti; J. David Williamson, III; James E. Carpenter (Annals of Biomedical Engineering, 2002)

Density functional calculation of pK a values and redox potentials in the bovine Rieske iron-sulfur protein - Matthias G. Ullmann; Louis Noodleman; David A. Case (JBIC Journal of Biological Inorganic Chemistry, 2002)

The GLOBEC Northeast Pacific California Current System Program - Harold Batchhelder; John Barth; Michael Kosro; Ted Strub; Richard Brodeur; William Peterson; Cynthia Tynan; Mark Ohman; Louis Botsford; Thomas Powell; Franklin Schwing; David Ainley; et al. (Oceanography, 2002)

Differentiation at a microgeographical scale within two species of ground beetle, Carabus auronitens and C. nemoralis (Coleoptera, Carabidae): a geometrical morphometric approach - Paul Alibert; Benoit Moureau; Jean‐Louis Dommergues; Bruno David (Zoologica Scripta, 2001)
New morphometric methods, the geometrical morphometrics, offer promising perspectives to appraise morphological variation among organisms and open up, to a large extent, the field of morphometrics for the study of systematics and evolution. Until now, however, few studies have explored the potential of these methods at a microgeographical scale. In the present work, we applied them to quantify morphological (size and shape) differentiation among populations of two forest species of ground beetles: Carabus auronitens and C. nemoralis . We found a significant shape variation among sites, as well as among sexes, for both species. Additionally, for C. auronitens , we found significant positive correlations in both sexes between morphological (shape) and geographical distances between populations. In contrast, significant size differences were found between sexes, but not between sites. We conclude that geometrical morphometric methods provide valuable tools for the study of morphological variation among populations and therefore offer, on the whole, interesting perspectives for the study of biodiversity patterns.

Expression of neural cell adhesion molecule in human liver development and in congenital and acquired liver diseases - Louis Libbrecht; David Cassiman; Valeer Desmet; Tania Roskams (Histochemistry and Cell Biology, 2001)

Isolation and characterization of microsatellite loci in the yellow perch ( Perca flavescens ), and cross‐ species amplification within the family Percidae - David Leclerc; Thierry Wirth; Louis Bernatchez (Molecular Ecology, 2000)

Accurate scale up of two phase flow using renormalization and nonuniform coarsening - Timothy C. Wallstrom; Shuling Hou; Michael A. Christie; Louis J. Durlofsky; David H. Sharp (Computational Geosciences, 1999)

Antidepressant effects of nicotine in an animal model of depression - Y. Tizabi; David H. Overstreet; Amir H. Rezvani; Vely A. Louis; Elijah Clark Jr; David S. Janowsky; Mitchel A. Kling (Psychopharmacology, 1999)

Biome reconstruction from pollen and plant macrofossil data for Africa and the Arabian peninsula at 0 and 6000 years - Dominique Jolly; I. Colin Prentice; Raymonde Bonnefille; Aziz Ballouche; Martin Bengo; Patrice Brenac; Guillaume Buchet; David Burney; Jean‐Pierre Cazet; Rachid Cheddadi; Therese Edorh; Hilaire Elenga; et al. (Journal of Biogeography, 1998)
Biome reconstruction from pollen and plant macrofossil data provides an objective method to reconstruct past vegetation. Biomes for Africa and the Arabian peninsula have been mapped for 6000 years bp and provide a new standard for the evaluation of simulated palaeovegetation distributions. A test using modern pollen data shows the robustness of the biomization method, which is able to predict the major vegetation types with a high confidence level. The application of the procedure to the 6000 years data set (pollen and plant macrofossil analyses) shows systematic differences from the present that are consistent with the numerous previous regional and continental interpretations, while providing a more extensive and more objective basis for such interpretations. Madagascar, eastern, southern and central Africa show only minor changes in terms of biomes, compared to present. Major changes in biome distributions occur north of 15°N, with steppe in many low‐elevation sites that are now desert, and temperate xerophytic woods/scrub and warm mixed forest in the Saharan mountains. These shifts in biome distributions imply significant changes in climate, especially precipitation, between 6000 years and present, reflecting a change in monsoon extent combined with a southward expansion of Mediterranean influence.

Isradipine prevents global and regional cocaine-induced changes in brain blood flow: a preliminary study - B. Johnson; Bruce Barron; Bing Fang; L. Lamki; Louis Wagner; Lynda Wells; Paul Kenny; Dennis Overton; Sukhindar Dhother; David Abramson; Richard Chen; Larry Kramer (Psychopharmacology, 1998)

Modeled responses of terrestrial ecosystems to elevated atmospheric CO 2 : a comparison of simulations by the biogeochemistry models of the Vegetation/Ecosystem Modeling and Analysis Project (VEMAP) - Yude Pan; Jerry M. Melillo; A. David McGuire; David W. Kicklighter; Louis F. Pitelka; Kathy Hibbard; Lars L. Pierce; Steven W. Running; Dennis S. Ojima; William J. Parton; David S. Schimel (Oecologia, 1998)

Cycling and Accumulation of Biogenic Silica and Organic Matter in High-Latitude Environments: The Ross Sea - David DeMaster; Robert Dunbar; Louis Gordon; Amy Leventer; John Morrison; David Nelson; Charles Nittrouer; Walker Smith (Oceanography, 1992)